Adhesive composition, bonding film, laminate with adhesive composition layer, laminate, and electromagnetic wave shielding film

By using adhesive compositions of polyester polyamide resin and epoxy resin, combined with components such as polyurethane resin, conductive fillers and imidazole compounds, the appearance abnormalities of existing adhesives when used in high temperature and high humidity environments are solved. and the problem of reducing strength, efficient welding heat resistance and long-term humidity and heat resistance are achieved.

CN119452058APending Publication Date: 2025-02-14TOAGOSEI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380050685.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When used in high-temperature and high-humidity environments, existing adhesives are prone to problems of abnormal appearance or reduced strength, and drying is required to avoid these problems and affect production efficiency.

Method used

The adhesive composition including a polyester polyamide resin and an epoxy resin is used, and the amount of the epoxy resin is 1 to 60 parts by mass relative to 100 parts by mass of the polyester polyamide resin, and polyurethane is added to the composition. Components such as resin, conductive filler, imidazole compounds having an alkoxy silyl group.

Benefits of technology

It achieves excellent heat resistance of welding in normal wet environments and excellent long-term humidity and heat resistance, avoids the need for drying treatment and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215104160000201
    Figure BDA0005215104160000201
  • Figure BDA0005215104160000211
    Figure BDA0005215104160000211
  • Figure BDA0005215104160000212
    Figure BDA0005215104160000212
Patent Text Reader

Abstract

The adhesive composition of the present disclosure contains a polyester polyamide resin (A) having a polyester moiety and a polyamide moiety, and an epoxy resin (B). The amount of the epoxy resin (B) is 1-60 parts by mass per 100 parts by mass of the polyester polyamide resin (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition, a bonding film, a laminate having an adhesive composition layer, a laminate, and an electromagnetic wave shielding film. Background Art

[0002] Since the flexible printed circuit board can be installed three-dimensionally and at a high density even in a limited space, its use is expanding. In recent years, with the miniaturization and lightweight of electronic equipment, the related products of the flexible printed circuit board have been diversified, and its demand is increasing. As such related products, there are flexible copper-clad laminated boards with copper foil bonded on polyimide films, flexible printed circuit boards with electronic circuits formed on flexible copper-clad laminated boards, flexible printed circuit boards with reinforcing plates bonded to flexible printed circuit boards and reinforcing plates, overlapping and joining flexible copper-clad laminated boards or multilayer boards of flexible printed circuit boards, etc. In the case of manufacturing flexible copper-clad laminated boards, in order to bond polyimide films to copper foil, adhesives are usually used.

[0003] As conventional adhesive compositions or conventional laminates, methods described in Patent Documents 1 to 6 are known. An adhesive is described in Patent Document 1. The adhesive described in Patent Document 1 is composed of a polyester amide resin (A) having an acid value of 100 to 2000 equivalents / t and an epoxy compound (B).

[0004] Patent document 2 describes an adhesive tape for TAB. The adhesive tape described in Patent document 2 is formed by providing an adhesive layer containing at least polyamide resin, epoxy resin and phenolic resin on an organic insulating film. The elastic modulus of the adhesive layer at 100°C is 200 to 500 MPa, and the elastic modulus at 180°C is 10 to 100 MPa.

[0005] Patent document 3 describes an adhesive resin composition. The adhesive resin composition described in Patent document 3 comprises (A) a curing component containing an epoxy resin and a curing agent, (B) a polyamide soluble in an aprotic solvent, (C) a flame retardant, and (D) a solvent. The epoxy resin comprises a phenol aralkyl type epoxy resin. The solvent consists of an aprotic solvent. The weight fraction of the component (A) relative to the total weight of the component (A) and the component (B) is 41 to 70 weight %.

[0006] Patent document 4 describes a thermosetting adhesive composition. The thermosetting adhesive composition described in Patent document 4 contains a (meth) acrylic polymer having a glass transition temperature of 5°C or more, a liquid epoxy resin, a solid resin, a polyamide elastomer having a reactive functional group at the end, and an epoxy resin curing agent. The solid resin is one or more selected from solid epoxy resins and solid phenolic resins. The solid resin is compatible with the liquid epoxy resin. The solid resin has a softening point of 50°C or more and 100°C or less.

[0007] Patent Document 5 describes a polyester amide resin composition. The polyester amide resin composition described in Patent Document 5 contains 1 to 50 parts by weight of a polyester amide resin having a polyamide repeating unit of a specific structure and 99 to 50 parts by weight of a positive or negative electrode active material.

[0008] Patent Document 6 describes an adhesive composition. The adhesive composition described in Patent Document 6 contains 1 to 300 parts by weight of one or more of styrene-isobutylene-styrene olefin elastomer, styrene-ethylene-butylene-styrene olefin elastomer, and maleic anhydride-modified products thereof, based on 100 parts by weight of polyetheresteramide.

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-152015 Patent Document 2: Japanese Patent Application Publication No. 2009-40814 Patent Document 3: Japanese Patent Application Publication No. 2012-25888 Patent Document 4: Japanese Patent Application Publication No. 2015-193683 Patent Document 5: Japanese Patent Application Publication No. 2010-31099 Patent Document 6: International Publication No. 2012 / 011265 Summary of the invention Technical problem to be solved by the invention

[0010] In the reflow soldering process of flexible printed circuit boards, if rapid heating is performed, the adhesive used may absorb moisture or decompose gas, which may cause abnormal appearance (such as expansion) or reduced strength. Therefore, a drying process is usually performed before the reflow soldering process. However, in recent years, in order to improve productivity, adhesives that do not require such drying processes are required. In view of the use environment of flexible wiring boards, adhesives whose strength is not reduced even after long-term storage at high temperature and high humidity are required.

[0011] The technical problem to be solved by the present invention is to provide an adhesive composition whose obtained cured product has excellent soldering heat resistance even in a normal humidity environment and also has excellent long-term moisture and heat resistance. Another technical problem to be solved by the present invention is to provide a bonding film using the adhesive composition, a laminate with an adhesive composition layer, a laminate, or an electromagnetic wave shielding film. Solutions to technical problems

[0012] The means for solving the technical problem include the following methods. <1> An adhesive composition comprising: A polyester polyamide resin (A) having a polyester portion and a polyamide portion; and an epoxy resin (B) wherein the amount of the epoxy resin (B) is 1 to 60 parts by mass based on 100 parts by mass of the polyester polyamide resin (A). <2> The adhesive composition according to <1>, wherein the polyester polyamide resin (A) has an amine value of 1.0 mgKOH / g to 12.0 mgKOH / g. <3> The adhesive composition according to <1> or <2>, wherein the polyester portion of the polyester polyamide resin (A) is a condensation product of an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and an aliphatic diol having 2 to 54 carbon atoms, an aromatic diol having 2 to 54 carbon atoms or an alicyclic diol having 2 to 54 carbon atoms, The polyamide portion of the polyester polyamide resin (A) is a condensation product of a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimerized aliphatic diacid having 20 to 48 carbon atoms and an aromatic diamine having 6 to 44 carbon atoms and / or a diamine having an alicyclic skeleton having 6 to 44 carbon atoms. <4> The adhesive composition according to any one of <1> to <3>, further comprising a polyurethane resin (C). <5> The adhesive composition according to any one of <1> to <4>, wherein a cured product thereof has a water absorption of 3% or less when immersed in water at 23°C for 24 hours. <6> The adhesive composition according to any one of <1> to <5>, further comprising a conductive filler (D). <7> The adhesive composition according to <6>, wherein the content of the conductive filler (D) is 10 to 350 parts by mass based on 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B), and the polyester urethane resin (C) which may be contained as an optional component in the adhesive composition. <8> The adhesive composition according to any one of <1> to <7>, further comprising an imidazole compound (E) having an alkoxysilyl group. <9> The adhesive composition according to any one of <1> to <8>, further comprising an inorganic filler (F) that does not have electrical conductivity. <10> The adhesive composition according to any one of <1> to <9>, further comprising a non-conductive organic filler (G). <11> A bonding film comprising: an adhesive composition layer in a B-stage state formed by partially curing the adhesive composition according to any one of <1> to <10>; and a release film in contact with at least one surface of the adhesive composition layer. <12> A laminate with an adhesive composition layer, comprising: an adhesive composition layer and a base film in contact with at least one surface of the adhesive composition layer; The adhesive composition layer is an adhesive composition layer composed of an uncured material of the adhesive composition according to any one of <1> to <10>, an adhesive composition layer in a B-stage state in which a portion of the adhesive composition is cured, or a cured layer in which the adhesive composition is cured. <13> A laminate comprising a cured layer formed by curing the adhesive composition according to any one of <1> to <10>. <14> An electromagnetic wave shielding film comprising a cured layer formed by curing the adhesive composition according to any one of <1> to <10>. Effects of the Invention

[0013] According to one embodiment of the present invention, it is possible to provide an adhesive composition in which the obtained cured product has excellent soldering heat resistance even in a normal humidity environment and also has excellent long-term moisture and heat resistance. According to one embodiment of the present invention, there can be provided a bonding film using the adhesive composition, a laminate with an adhesive composition layer, a laminate, or an electromagnetic wave shielding film. DETAILED DESCRIPTION

[0014] The description of the constituent elements described below may be based on representative embodiments of the present disclosure, but the present disclosure is not limited to such embodiments. In the present specification, "to" is used to include the numerical values ​​described before and after it as the lower limit and the upper limit. In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment. In the present disclosure, when a plurality of substances corresponding to each component are present in a composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition unless otherwise specified. In the present disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. In the present disclosure, "mass %" and "weight %" have the same meaning, and "parts by mass" and "parts by weight" have the same meaning. In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In this specification, "(meth)acrylic acid" means both or either acrylic acid and methacrylic acid. In some of the compounds in the present specification, a hydrocarbon chain may be described as a simplified structural formula in which the symbols of carbon (C) and hydrogen (H) are omitted. Next, the contents of the present disclosure are described in detail.

[0015] (Adhesive composition) The adhesive composition of the present disclosure comprises a polyester polyamide resin (A) having a polyester part and a polyamide part and an epoxy resin (B). The amount of the epoxy resin (B) is 1 to 60 parts by mass based on 100 parts by mass of the polyester polyamide resin (A). The adhesive composition of the present disclosure can be suitably used as an adhesive composition for bonding polyimide or metal, and is particularly suitably used as an adhesive composition for bonding polyimide and metal.

[0016] The present inventors have found that cured products of conventional adhesive compositions have insufficient soldering heat resistance in a normal humidity environment. As described above, there is a demand for adhesive compositions that do not lose strength or the like even after long-term storage under high temperature and high humidity. The present inventors have conducted intensive studies and have found that, by including a polyester polyamide resin (A) having a polyester portion and a polyamide portion and an epoxy resin (B), the amount of the epoxy resin (B) is 1 to 60 parts by mass relative to 100 parts by mass of the polyester polyamide resin (A), an adhesive composition can be provided in which the obtained cured product has excellent soldering heat resistance even in a normal humidity environment and also has excellent long-term moisture-heat resistance. The detailed mechanism of this effect is not yet clear, but it is speculated to be based on the following reasons. The polyester polyamide resin (A) and the epoxy resin (B) act synergistically with each other and complement each other. In addition, by constituting the polyester part of the polyester polyamide resin (A), the hydrophobicity of the resin is improved and the moisture resistance is improved. Therefore, the moisture absorption rate of the obtained cured product is low. The water absorption of the obtained cured product can be suppressed for a long time even under high temperature and high humidity. The adhesion of the obtained cured product can also be maintained for a long time. The obtained cured product has excellent welding heat resistance even in a normal humidity environment, and also excellent long-term moisture and heat resistance.

[0017] The adhesive composition disclosed herein comprises a polyester polyamide resin (A) having a polyester portion and a polyamide portion and an epoxy resin (B). The amount of the epoxy resin (B) is 1 to 60 parts by mass relative to 100 parts by mass of the polyester polyamide resin (A). The adhesive composition disclosed herein has excellent adhesion and storage stability due to the above-mentioned structure.

[0018] Hereinafter, the present disclosure will be described in detail. In this specification, "polyester polyamide resin (A) etc. may also be referred to as "component (A) etc.".

[0019] <Polyester polyamide resin (A)> The adhesive composition of the present disclosure contains a polyester polyamide resin (A). The polyester polyamide resin (A) comprises a polyester portion and a polyamide portion. The polyester part has two or more ester bonds. The polyamide part has two or more amide bonds. The polyester part and the polyamide part can be combined via an ester bond or an amide bond. The polyester polyamide resin (A) can be a resin having two or more ester bonds and two or more amide bonds. The polyester polyamide resin (A) is preferably a resin having a polyester chain and two or more amide bonds, a resin having a polyamide chain and two or more ester bonds, a resin having a polyester chain and a polyamide chain, etc. The weight average molecular weight of the polyester chain can be more than 1,000. The weight average molecular weight of the polyamide chain can be more than 1,000. The upper limit of the weight average molecular weight of each polyester chain and polyamide chain is not particularly limited, for example, it can be 150,000 or less. The raw material of the polyester polyamide resin (A) is preferably a resin obtained by reacting at least a polycarboxylic acid, a polyol, and a polyamine, and more preferably a resin obtained by reacting at least a dicarboxylic acid, a diol, and a diamine. The polyester polyamide resin (A) is preferably a linear resin. The polyester polyamide resin (A) preferably has no aromatic ring. By using a linear polyester polyamide resin (A) having no aromatic ring, the processability in hot pressing or hot lamination can be improved.

[0020] The polyester portion in the polyester polyamide resin (A) is preferably composed of an acid component and an alcohol component. As the acid component, a polycarboxylic acid compound is preferred, and a dicarboxylic acid compound is more preferred. As the acid component, a sulfocarboxylic acid compound or the like can also be used. In addition, as the acid component, an aliphatic acid can be preferably mentioned. The alcohol component is preferably a polyol compound, more preferably a diol compound. The polyester portion may be formed from a hydroxycarboxylic acid compound.

[0021] Examples of the aromatic acid include aromatic dicarboxylic acids and aromatic hydroxycarboxylic acids, etc. Examples of the aromatic dicarboxylic acid include aromatic dicarboxylic acids not having at least one of a sulfonic acid group and a sulfonate group, and aromatic dicarboxylic acids having a sulfonic acid group or a sulfonate group. Examples of the aromatic dicarboxylic acid not having at least one of a sulfonic acid group and a sulfonate group include terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, and 5-hydroxyisophthalic acid. Examples of the aromatic dicarboxylic acid having a sulfonic acid group or a sulfonate group include sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-(4-sulfophenoxy)isophthalic acid, sulfoterephthalic acid, metal salts thereof, and ammonium salts thereof. Examples of the aromatic hydroxycarboxylic acid include p-hydroxybenzoic acid, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, and 4,4-bis(p-hydroxyphenyl)valeric acid. The acid component may be a derivative of an acid compound such as an ester during resin synthesis.

[0022] Examples of the aliphatic acid component include alicyclic dicarboxylic acids and aliphatic dicarboxylic acids. Examples of the alicyclic dicarboxylic acid include 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, and anhydrides thereof. Examples of the aliphatic dicarboxylic acid include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, and dimer acid. Among them, from the viewpoint of welding durability and adhesiveness, it is preferred to contain azelaic acid and / or dimer acid as the acid component, and it is particularly preferred to contain azelaic acid. From the viewpoint of welding durability and adhesiveness, the acid component is preferably an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms, or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms, and more preferably an aliphatic dicarboxylic acid having 6 to 22 carbon atoms or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms.

[0023] Preferred examples of the polyol component include aliphatic diol compounds, alicyclic diol compounds, aromatic diol compounds, and ether bond-containing diol compounds. Examples of the aliphatic diol compound include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, 2-butyl-2-ethyl-1,3-propanediol, hydroxypivalic acid neopentyl glycol ester, dimethylolheptane, and 2,2,4-trimethyl-1,3-pentanediol. Examples of the alicyclic diol compound include 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, tricyclodecanediol, tricyclodecane dimethanol, spiroglycol, hydrogenated bisphenol A, and ethylene oxide adducts and propylene oxide adducts of hydrogenated bisphenol A. Examples of the aromatic diol compound include p-xylene glycol, m-xylene glycol, o-xylene glycol, 1,4-phenylene glycol, ethylene oxide adducts of 1,4-phenylene glycol, bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts, which are diols obtained by adding 1 to several moles of ethylene oxide or propylene oxide to each of the two phenolic hydroxyl groups of bisphenols. Examples of the diol compound containing an ether bond include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, neopentyl glycol ethylene oxide adducts, and neopentyl glycol propylene oxide adducts. Among these diols, diols having a side chain (for example, neopentyl glycol or 2-butyl-2-ethyl-1,3-propanediol) are preferred from the perspective of compatibility with epoxy resins and the like and solution stability. That is, from the viewpoint of compatibility with epoxy resins and the like and solution stability, the diol component constituting the polyester polyamide resin (A) preferably contains a diol having a side chain. The side chain in the diol having a side chain is preferably an alkyl group, and the number of carbon atoms in the alkyl group may be, for example, 1, 2, 3, 4, or 5. This also applies to the diol having a side chain described below. Examples of the diol having a side chain include neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, and 2,2-dimethylolpropionic acid.

[0024] As the polyester raw material, a hydroxycarboxylic acid compound having a hydroxyl group and a carboxyl group in the molecular structure can be used. Examples of the hydroxycarboxylic acid compound include 5-hydroxyisophthalic acid, p-hydroxybenzoic acid, p-hydroxyphenylethanol, p-hydroxyphenylpropionic acid, p-hydroxyphenylacetic acid, 6-hydroxy-2-naphthoic acid, and 4,4-bis(p-hydroxyphenyl)valeric acid.

[0025] In order to introduce a branched skeleton into the components constituting the polyester part of the polyester polyamide resin (A) as needed, trifunctional or higher polycarboxylic acids and / or polyols may be copolymerized. The amount of trifunctional or higher polycarboxylic acids and / or polyols is about 0.1 mol% to 5 mol% relative to the total acid components or the total polyol components constituting the polyester part. In particular, when a cured layer is obtained by reacting with a curing agent, the terminal group concentration (reaction point) of the resin is increased by introducing a branched skeleton, and a cured layer with a high crosslinking density can be obtained. Examples of trifunctional or higher polycarboxylic acids include trimellitic acid, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tri(anhydrotrimellitate), trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic anhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). Examples of trifunctional or higher polyols include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol. The amount of the trifunctional or higher polycarboxylic acid and / or polyol is preferably 0.1 mol% to 5 mol%, more preferably 0.1 mol% to 3 mol%, based on the total acid components or the total polyol components. Among them, from the viewpoint of soldering heat resistance and adhesiveness, the polyester portion of the polyester polyamide resin (A) is preferably a polycondensate of an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and an aliphatic diol having 2 to 54 carbon atoms, an aromatic diol having 2 to 54 carbon atoms or an alicyclic diol having 2 to 54 carbon atoms.

[0026] In the present disclosure, “aliphatic dicarboxylic acid having 6 to 22 carbon atoms, aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or alicyclic dicarboxylic acid having 6 to 22 carbon atoms” includes: Aliphatic dicarboxylic acids having 6 to 22 carbon atoms, aromatic dicarboxylic acids having 6 to 22 carbon atoms, and alicyclic dicarboxylic acids having 6 to 22 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms and aromatic dicarboxylic acids having 6 to 22 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms and alicyclic dicarboxylic acids having 6 to 22 carbon atoms; Aromatic dicarboxylic acids having 6 to 22 carbon atoms and alicyclic dicarboxylic acids having 6 to 22 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms; Aromatic dicarboxylic acids having 6 to 22 carbon atoms; and Alicyclic dicarboxylic acid having 6 to 22 carbon atoms. In the present disclosure, “aliphatic diol having 2 to 54 carbon atoms, aromatic diol having 2 to 54 carbon atoms, or alicyclic diol having 2 to 54 carbon atoms” includes: Aliphatic diols having 2 to 54 carbon atoms; Aromatic diols having 2 to 54 carbon atoms; and Alicyclic diols having 2 to 54 carbon atoms.

[0027] In order to introduce carboxyl groups as needed, the polyester portion of the polyester polyamide resin (A) may be subjected to acid addition. The amount of acid addition is about 0.1 mol% to 10 mol% relative to the total acid components or the total polyol components constituting the polyester portion. If a monocarboxylic acid, a dicarboxylic acid, or a polyfunctional carboxylic acid compound is used in the acid addition, it is possible that the molecular weight may be reduced due to transesterification. Therefore, it is preferred to use an acid anhydride in the acid addition. Examples of the acid anhydride include succinic anhydride, maleic anhydride, phthalic acid, 2,5-norbornene dicarboxylic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic anhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). The acid addition method includes, for example, a method of directly performing the acid addition in a bulk state after polyester polycondensation, and a method of performing the acid addition after the polyester is dissolved. The reaction speed in the bulk state is fast. However, in the reaction in the bulk state, if a large amount of acid addition is performed on the polyester part of the polyester polyamide resin (A), gelation sometimes occurs, and the reaction temperature in the bulk state is high. Therefore, in the reaction in the bulk state, it is necessary to pay attention to blocking oxygen to prevent oxidation, etc. In the acid addition in the solution state, the reaction is slow, but a large amount of carboxyl groups can be stably introduced into the polyester part of the polyester polyamide resin (A).

[0028] The polyamide portion in the polyester polyamide resin (A) is preferably composed of an acid component and an amine component. As the acid component, a polycarboxylic acid compound is preferred, and a dicarboxylic acid compound is more preferred. As the acid component, a sulfocarboxylic acid compound and an aliphatic acid can be used. Preferred examples of the acid component include the acid components described above as the acid component of the polyester part. Among them, from the viewpoint of soldering heat resistance and adhesiveness, the polyamide portion of the polyester polyamide resin (A) preferably contains a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms, or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimer aliphatic diacid having 20 to 48 carbon atoms, more preferably contains a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimer aliphatic diacid having 20 to 48 carbon atoms, and particularly preferably contains azelaic acid. The aliphatic, aromatic or alicyclic dicarboxylic acid preferably has 6 to 12 carbon atoms, more preferably 8 to 10 carbon atoms. The dimerized aliphatic diacid preferably has 30-48 carbon atoms, more preferably 32-40 carbon atoms.

[0029] The amine component is preferably a polyamine compound, more preferably a diamine compound. The polyamide portion may be formed from an aminocarboxylic acid compound.

[0030] Examples of the diamine compound include diaminocyclohexane, piperidine, isophoronediamine, 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, o-(or m-, p-)phenylenediamine, o-(or m-, p-)xylene diamine, 3,3'-(or 3,4'-)diaminodiphenyl ether, 4-(4-amino)phenylene glycol ...1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, o-(or m-, p-)phenylenediamine, o-(or m-, p-)xylene diamine, 3,3'-(or 3,4'-)diaminodiphenyl ether, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-di ,4'-diaminodiphenyl ether, 3,3'-(or 3,4'-) diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,3'-(or 3,4'-, 4,4'-) diaminodiphenyl difluoromethane, 3,3'-(or 3,4'-, 4,4'-) diaminodiphenyl sulfone, 3,3'-(or 3,4'-, 4,4'-) diaminodiphenyl sulfide, 3,3'-(or 3,4'-, 4,4'-) diaminodiphenyl Benzophenone, 2,2-bis(3-aminophenyl)propane, 2,2'-(3,4'-diaminodiphenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2-(3,4'-diaminodiphenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 1,3-(or 1,4-)bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 3 ,3'-(1-phenylenebis(1-methylethylidene))dianiline, 3,4'-(1,4-phenylenebis(1-methylethylidene))dianiline, 4,4'-(1,4-phenylenebis(1-methylethylidene))dianiline, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, and 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, etc.

[0031] Among them, as the amine component, from the viewpoint of soldering heat resistance, it is preferred to contain a diamine having an aromatic or alicyclic skeleton having 6 to 44 carbon atoms, more preferably a diamine having an alicyclic skeleton having 6 to 44 carbon atoms, and particularly preferably isophoronediamine. The diamine preferably has 8 to 30 carbon atoms, and more preferably 10 to 24 carbon atoms.

[0032] Among them, from the viewpoints of soldering heat resistance, adhesiveness and conductivity, the polyamide portion of the polyester polyamide resin (A) is preferably a polycondensate of a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimerized aliphatic diacid having 20 to 48 carbon atoms, and an aromatic diamine having 6 to 44 carbon atoms and / or an alicyclic skeleton having 6 to 44 carbon atoms, and more preferably a polycondensate of a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimerized aliphatic diacid having 20 to 48 carbon atoms and a diamine having an alicyclic skeleton having 6 to 44 carbon atoms.

[0033] In the present disclosure, “aliphatic dicarboxylic acids having 6 to 22 carbon atoms, aromatic dicarboxylic acids having 6 to 22 carbon atoms and / or alicyclic dicarboxylic acids having 6 to 22 carbon atoms and / or dimerized aliphatic diacids having 20 to 48 carbon atoms” include: Aliphatic dicarboxylic acids having 6 to 22 carbon atoms, aromatic dicarboxylic acids having 6 to 22 carbon atoms, alicyclic dicarboxylic acids having 6 to 22 carbon atoms, and dimerized aliphatic diacids having 20 to 48 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms and dimerized aliphatic diacids having 20 to 48 carbon atoms; Aromatic dicarboxylic acids having 6 to 22 carbon atoms and dimerized aliphatic diacids having 20 to 48 carbon atoms; Alicyclic dicarboxylic acids having 6 to 22 carbon atoms and dimerized aliphatic diacids having 20 to 48 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms, aromatic dicarboxylic acids having 6 to 22 carbon atoms, and alicyclic dicarboxylic acids having 6 to 22 carbon atoms; Aliphatic dicarboxylic acids having 6 to 22 carbon atoms; Aromatic dicarboxylic acids having 6 to 22 carbon atoms; an alicyclic dicarboxylic acid having 6 to 22 carbon atoms; and A dimerized aliphatic diacid having 20 to 48 carbon atoms.

[0034] The polyester portion of the polyester polyamide resin (A) is a polycondensate of an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and an aliphatic diol having 2 to 54 carbon atoms, an aromatic diol having 2 to 54 carbon atoms or an alicyclic diol having 2 to 54 carbon atoms, The polyamide portion of the polyester polyamide resin (A) is preferably a polycondensate of a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimerized aliphatic diacid having 20 to 48 carbon atoms and an aromatic diamine having 6 to 44 carbon atoms and / or a diamine having an alicyclic skeleton having 6 to 44 carbon atoms. This makes it possible to provide an adhesive composition having low water absorption and excellent long-term moisture and heat resistance.

[0035] When producing the polyester polyamide resin (A), a chain extender may be used as necessary. Examples of the chain extender include the diol compounds described above as constituent components of the polyester portion, and compounds having one carboxyl group and two hydroxyl groups (eg, dimethylolpropionic acid, dimethylolbutanoic acid, etc.). Among them, as the chain extender, from the viewpoint of conductivity, a diol compound is preferred, a diol compound having a side chain is more preferred, and a diol compound having a branched chain is particularly preferred. From the viewpoint of conductivity, the diol compound having a side chain preferably includes at least one compound selected from the group consisting of neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol and 2,2-dimethylolpropionic acid. The diol compound having a side chain particularly preferably includes at least one compound selected from the group consisting of neopentyl glycol and 2-butyl-2-ethyl-1,3-propanediol and 2,2-dimethylolpropionic acid. As the chain extender, a polyamine compound can be used.

[0036] There is no particular limitation on the method for producing the polyester polyamide resin (A), and a known method can be used. For example, polycarboxylic acid, polyol and polyamine can be added to the reaction vessel together with the chain extender as required, or they can be added separately. In short, relative to the total of the hydroxyl value and amine value of the polyol and polyamine in the system and the total of the carboxyl group of the polycarboxylic acid, the ratio of the functional groups of carboxyl / hydroxyl and amino is preferably 0.9 or more and 1.1 or less, more preferably 0.98 or more and 1.02 or less, and particularly preferably 1. The reaction can be produced by reacting it in the presence or absence of a solvent. As a solvent, for example, ester solvents (for example, ethyl acetate, butyl acetate, ethyl butyrate, etc.), ether solvents (for example, dioxane, tetrahydrofuran, diethyl ether, etc.), ketone solvents (for example, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, etc.), aromatic hydrocarbon solvents (for example, benzene, toluene, xylene, etc.) and their mixed solvents, etc. As a solvent, from the viewpoint of reducing environmental load, ethyl acetate or methyl ethyl ketone is preferred. The reaction apparatus is not limited to a reaction tank equipped with a stirring device, and a mixing and kneading device such as a kneader and a twin-screw extruder may be used. In order to promote the esterification or amidation reaction, a catalyst commonly used in esterification and / or amidation reaction (for example, tetrabutoxytitanate, etc.) can be used. If necessary, a condensation agent or the like can also be used.

[0037] From the viewpoints of adhesion, conductivity and heat resistance, the glass transition temperature (Tg) of the polyester portion in the polyester polyamide resin (A) is preferably 40°C to 150°C, more preferably 45°C to 120°C, further preferably 50°C to 90°C, particularly preferably 60°C to 70°C. The glass transition temperature (Tg) of the polyester polyamide resin (A) is preferably 30 to 150°C, more preferably 40 to 140°C, further preferably 50 to 90°C, particularly preferably 60 to 70°C, from the viewpoints of adhesion, conductivity and heat resistance.

[0038] From the viewpoint of soldering heat resistance, electrical conductivity and heat resistance, the weight average molecular weight (Mw) of the polyester polyamide resin (A) is preferably 5,000 to 150,000, more preferably 10,000 to 100,000, further preferably 30,000 to 80,000, and particularly preferably 40,000 to 60,000. From the viewpoint of soldering heat resistance, electrical conductivity and heat resistance, the number average molecular weight (Mn) of the polyester polyamide resin (A) is preferably 1,500 to 50,000, more preferably 10,000 to 25,000, and further preferably 13,000 to 20,000. The values ​​of the number average molecular weight (Mn) and the weight average molecular weight (Mw) of the resin in the present disclosure refer to values ​​obtained by converting the molecular weight measured by gel permeation chromatography (hereinafter also referred to as “GPC”) under the following conditions into polystyrene. <Measurement conditions> Device: Tosoh Corporation model number "HLC-8320" Column: TSKgel SuperMultiporeHZ-M manufactured by Tosoh Corporation × 4 Solvent: Tetrahydrofuran Column temperature: 40°C Detector: RI Flow rate: 600 μL / min

[0039] From the viewpoint of soldering heat resistance, adhesion and conductivity, the amine value of the polyester polyamide resin (A) is preferably 1.0 mgKOH / g to 12.0 mgKOH / g, more preferably 3.0 mgKOH / g to 11.0 mgKOH / g, further preferably 6.0 mgKOH / g to 10.0 mgKOH / g, and particularly preferably 7.0 mgKOH / g to 8.0 mgKOH / g. The amine value of the resin in the present disclosure is measured and calculated by a potential difference measurement method in accordance with JIS K 7237 (1995).

[0040] The adhesive composition of the present disclosure may contain one type of the polyester polyamide resin (A) alone, or may contain two or more types. From the viewpoint of adhesion, conductivity and heat resistance, the content of the polyester polyamide resin (A) is preferably 5% to 98% by mass, more preferably 10% to 95% by mass, further preferably 20% to 90% by mass, and particularly preferably 30% to 85% by mass relative to the total solid content of the adhesive composition.

[0041] <Epoxy resin (B)> The adhesive composition of the present disclosure contains an epoxy resin (B). The epoxy resin (B) is a component that imparts adhesiveness or heat resistance to the cured portion after bonding. The epoxy resin (B) in the present disclosure includes not only polymer compounds having epoxy groups but also low molecular weight compounds having epoxy groups. The number of epoxy groups in the epoxy resin (B) is preferably 2 or more. Examples of the epoxy resin (B) include glycidyl esters, glycidyl ethers, and novolac-type epoxy resins. Examples of the glycidyl ester include diglycidyl phthalate, diglycidyl isophthalate, diglycidyl terephthalate, diglycidyl p-hydroxybenzoate, diglycidyl tetrahydrophthalate, diglycidyl succinate, diglycidyl adipate, diglycidyl sebacate, and triglycidyl trimellitate. Examples of the glycidyl ethers include diglycidyl ether of bisphenol A and oligomers thereof, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, tetraphenylglycidyl ether ethane, triphenylglycidyl ether ethane, polyglycidyl ethers of sorbitol, and polyglycidyl ethers of polyglycerol. Examples of the novolac epoxy resin include phenol novolac epoxy resin, o-cresol novolac epoxy resin, and bisphenol A novolac epoxy resin. As the epoxy resin (B), brominated bisphenol A type epoxy resin imparted with flame retardancy, phosphorus-containing epoxy resin, epoxy resin containing trisphenol methane skeleton, epoxy resin containing dicyclopentadiene skeleton, epoxy resin containing naphthalene skeleton, anthracene type epoxy resin, tert-butylcatechol type epoxy resin, biphenyl type epoxy resin and bisphenol S type epoxy resin can also be used. Among them, from the viewpoint of adhesiveness and solder heat resistance, the epoxy resin (B) preferably includes an epoxy resin containing a trisphenol methane skeleton.

[0042] In the present disclosure, in order to exhibit high heat resistance after curing, the epoxy resin (B) preferably contains a compound having three or more epoxy groups in one molecule. When such a compound is used, the crosslinking reactivity between the polyester urethane resin (A) and the resin (C) having a carboxyl group or a carboxylic anhydride structure is improved compared to the case where an epoxy resin having two epoxy groups in one molecule is used, and sufficient heat resistance can be obtained. From the viewpoint of heat resistance, the content of the compound having three or more epoxy groups in one molecule of the epoxy resin (B) is preferably 15% by mass or more, more preferably 20% by mass or more, particularly preferably 25% by mass or more, based on the total mass of the epoxy resin (B).

[0043] The adhesive composition of the present disclosure may contain one epoxy resin (B) alone, or two or more epoxy resins (B) may be contained. The content of the epoxy resin (B) is 1% to 60% by mass relative to 100 parts by mass of the polyester polyamide resin (A) in the adhesive composition, and is preferably 2% to 50% by mass, more preferably 5% to 40% by mass, and particularly preferably 10% to 40% by mass from the viewpoint of soldering heat resistance, adhesion and conductivity.

[0044] From the viewpoint of soldering heat resistance, adhesion and conductivity, the total amount of the polyester polyamide resin (A) and the epoxy resin (B) is preferably 50% by mass or more, more preferably 80% by mass or more, and may be 100% by mass, relative to the total solid content of the adhesive composition excluding fillers.

[0045] <Polyurethane resin (C)> The adhesive composition of the present disclosure preferably further contains a polyurethane resin (C). This can further reduce the water absorption. As the polyurethane resin (C), it is more preferred that a polyester polyurethane resin is further contained. The polyurethane resin (C) is not particularly limited, and a known polyurethane resin can be used. From the viewpoint of soldering heat resistance, adhesiveness, and conductivity, the polyurethane resin (C) is preferably a polyester polyurethane resin. The diisocyanate component constituting the polyester polyurethane resin preferably contains a diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms. The polyester polyurethane resin may be any resin having two or more ester bonds and two or more urethane bonds, and is preferably a resin having a polyester chain and two or more urethane bonds. The polyester polyurethane resin is preferably a resin obtained by reacting at least a polyester polyol, a polyisocyanate, and a chain extender. The polyester polyurethane resin is more preferably a resin obtained by reacting at least a polyester polyol, a polyisocyanate, and a diol compound.

[0046] The polyester portion in the polyester polyurethane resin is preferably formed of an acid component and an alcohol component. As the acid component, a polycarboxylic acid compound is preferred, and a dicarboxylic acid compound is more preferred. As the acid component, a sulfocarboxylic acid compound or the like can also be used. In addition, as the acid component, an aromatic acid can be preferably mentioned. Specific examples of the acid component include the specific examples of the acid component described above in the polyester polyamide resin (A). The alcohol component is preferably a polyol compound, more preferably a diol compound. Specific examples of the alcohol component include the specific examples of the alcohol component described above in the polyester polyamide resin (A). The polyester portion may be formed from a hydroxycarboxylic acid compound. From the viewpoint of adhesion, heat resistance and moisture-heat resistance, the amount of the aromatic acid is preferably 30 mol% or more, more preferably 45 mol% or more, and particularly preferably 60 mol% or more, based on 100 mol% of the total amount of all acid components constituting the polyester part of the polyester polyurethane resin.

[0047] In order to introduce a branched skeleton into the components of the polyester part constituting the polyester polyurethane resin as needed, trifunctional or higher polycarboxylic acids and / or polyols may be copolymerized. The amount of trifunctional or higher polycarboxylic acids and / or polyols is about 0.1 mol% to 5 mol% relative to the total acid components or the total polyol components constituting the polyester part. In particular, when a cured layer is obtained by reacting with a curing agent, by introducing a branched skeleton, the terminal group concentration (reaction point) of the resin is increased, and a cured layer with a high crosslinking density can be obtained. Examples of trifunctional or higher polycarboxylic acids include trimellitic acid, trimesic acid, ethylene glycol bis(anhydrotrimellitate), glycerol tri(anhydrotrimellitate), trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 3,3,4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic anhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). Examples of trifunctional or higher polyols include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol. The amount of the trifunctional or higher polycarboxylic acid and / or polyol is preferably 0.1 mol% to 5 mol%, more preferably 0.1 mol% to 3 mol%, based on the total acid components or the total polyol components.

[0048] In order to introduce carboxyl groups as needed, acid addition can be performed on the polyester portion of the polyester polyurethane resin. The amount of acid addition is about 0.1 mol% to 10 mol% relative to the total acid components or the total polyol components constituting the polyester portion. If monocarboxylic acids, dicarboxylic acids, or polyfunctional carboxylic acid compounds are used in the acid addition, there is a possibility that the molecular weight may be reduced due to transesterification. Therefore, it is preferred to use anhydrides in the acid addition. Examples of the acid anhydride include succinic anhydride, maleic anhydride, phthalic acid, 2,5-norbornene dicarboxylic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride (PMDA), oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-diphenylsulfonetetracarboxylic anhydride (DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), and 2,2'-bis[(dicarboxyphenoxy)phenyl]propane dianhydride (BSAA). The acid addition method can include a method of directly performing the acid addition in a bulk state after the polyester polycondensation, and a method of adding the acid after the polyester is dissolved. The reaction speed in the bulk state is fast. However, in the reaction in the bulk state, if a large amount of acid addition is performed on the polyester part of the polyester polyamide resin (A), gelation sometimes occurs, and the reaction temperature in the bulk state is high. Therefore, in the reaction in the bulk state, it is necessary to pay attention to blocking oxygen to prevent oxidation, etc. In the acid addition in the solution state, the reaction is slow, but a large amount of carboxyl groups can be stably introduced into the polyester part of the polyester polyamide resin (A).

[0049] The polyurethane portion of the polyester polyurethane resin is composed of at least a diisocyanate component. The diisocyanate component contains a diisocyanate compound having a hydrocarbon group with 8 to 14 carbon atoms. The methylene group in the hydrocarbon group may be substituted with a non-reactive bond (e.g., -O-, -S-, -CO-, -COO-, -OCO-, etc.). The amount of the diisocyanate compound having a hydrocarbon group with 8 to 14 carbon atoms in the diisocyanate component is usually 70 mol% or more, preferably 90 mol% or more, and may also be 100 mol%. The polyurethane portion of the polyester polyurethane resin may be composed of a monofunctional or trifunctional or higher-functional isocyanate component in addition to the diisocyanate component. The diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms preferably has 8 to 12 carbon atoms, more preferably 8 to 10 carbon atoms, from the viewpoint of conductivity of the obtained cured product after welding, long-term reliability testing, and thermal cycling testing. The diisocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms preferably has an alicyclic structure from the viewpoint of the electrical conductivity of the obtained cured product after welding, after a long-term reliability test, and after a thermal cycle test.

[0050] In the polyester polyurethane resin, from the viewpoint of adhesiveness, the amount of the diisocyanate component is preferably 5 to 50 molar equivalents relative to 1 molar equivalent of the polyester part. In other words, in the polyester polyurethane resin, from the viewpoint of adhesiveness, the amount of the urethane bond is preferably 10 to 100 molar equivalents relative to 1 molar equivalent of the polyester part.

[0051] The polyisocyanate used in the production of the polyester polyurethane resin may be one of diisocyanate, its dimer (uretdione), its trimer (isocyanurate, triol adduct, biuret), etc., or a mixture of two or more thereof. As the diisocyanate component, for example, diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 4,4'-diisocyanate diphenyl ether, m-xylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, methylenebis(4-cyclohexane diisocyanate), isophorone diisocyanate, norbornane diisocyanate, and norbornene diisocyanate may be mentioned. Among them, from the viewpoint of transparency and conductivity of the obtained cured product after welding, long-term reliability test and thermal cycle test, aliphatic or alicyclic diisocyanate compounds are preferred, and alicyclic diisocyanate compounds are particularly preferred. From the viewpoint of easy availability and conductivity after thermal cycle test, 1,3-bis(isocyanate methyl)cyclohexane, 1,4-bis(isocyanate methyl)cyclohexane, methylenebis(4-cyclohexyl diisocyanate) or norbornane diisocyanate is preferred, and 1,3-bis(isocyanate methyl)cyclohexane is particularly preferred.

[0052] When producing the polyester polyurethane resin, a chain extender may be used as necessary. Examples of the chain extender include the diol compounds already described as constituent components of the polyester portion, and compounds having one carboxyl group and two hydroxyl groups (eg, dimethylolpropionic acid, dimethylolbutanoic acid, etc.). Among them, as the chain extender, from the viewpoint of conductivity, a diol compound is preferred, a diol compound having a side chain is more preferred, and a diol compound having a branched chain is particularly preferred. From the viewpoint of conductivity, the diol compound having a side chain preferably includes at least one compound selected from the group consisting of neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol and 2,2-dimethylolpropionic acid. The diol compound having a side chain particularly preferably includes at least one compound selected from the group consisting of neopentyl glycol and 2-butyl-2-ethyl-1,3-propanediol and 2,2-dimethylolpropionic acid. As a chain extender, a polyamino compound may also be used. In one embodiment, the polyester polyurethane resin may preferably not contain a urea bond.

[0053] There is no particular limitation on the method for producing the polyester polyurethane resin, and a known method can be used. For example, the polyester polyol and the polyisocyanate, and the chain extender as required, can be added to the reaction vessel together, or separately. In short, relative to the total of the hydroxyl values ​​of the polyester polyol and the chain extender in the system and the total of the isocyanate group of the polyisocyanate, the ratio of the functional group of the isocyanate group / hydroxyl group is preferably 0.9 or more and 1.1 or less, more preferably 0.98 or more and 1.02 or less, and particularly preferably 1. The reaction can be produced by reacting in the presence or absence of a solvent inactive to the isocyanate group. As the solvent, ester solvents (such as ethyl acetate, butyl acetate, ethyl butyrate, etc.), ether solvents (such as dioxane, tetrahydrofuran, diethyl ether, etc.), ketone solvents (such as cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, etc.), aromatic hydrocarbon solvents (such as benzene, toluene, xylene, etc.) and mixed solvents thereof can be cited. As a solvent, ethyl acetate or methyl ethyl ketone is preferred from the viewpoint of reducing environmental load. The reaction apparatus is not limited to a reaction tank equipped with a stirring device, and a mixing and kneading device such as a kneader and a twin-screw extruder may be used.

[0054] In order to promote the carbamate reaction, a catalyst used in a common carbamate reaction can be used. As such a catalyst, for example, a tin catalyst (for example, trimethyltin laurate, dimethyltin dilaurate, trimethyltin hydroxide, dimethyltin dihydroxide, stannous octoate, etc.), a lead catalyst (for example, red oleate, red-2-ethylhexanoate, etc.), an amine catalyst (for example, triethylamine, tributylamine, morpholine, diazabicyclooctane, diazabicycloundecene, etc.) can be used.

[0055] From the viewpoints of adhesiveness, conductivity and heat resistance, the glass transition temperature (Tg) of the polyester portion in the polyester polyurethane resin is preferably 40°C to 150°C, more preferably 45°C to 120°C, further preferably 50°C to 90°C, particularly preferably 60°C to 70°C. The glass transition temperature (Tg) of the polyester polyurethane resin is preferably 30 to 150°C, more preferably 40 to 140°C, further preferably 50 to 90°C, particularly preferably 60 to 70°C, from the viewpoints of adhesiveness, conductivity and heat resistance.

[0056] From the viewpoint of electrical conductivity and heat resistance, the number average molecular weight (Mn) of the polyester polyurethane resin is preferably 5,000 to 100,000, more preferably 10,000 to 80,000, further preferably 20,000 to 60,000, and particularly preferably 25,000 to 50,000. From the viewpoint of electrical conductivity and heat resistance, the weight average molecular weight (Mw) of the polyester polyurethane resin is preferably 20,000 to 400,000, more preferably 40,000 to 320,000, and further preferably 80,000 to 240,000.

[0057] From the viewpoint of conductivity and heat resistance, the molecular weight per urethane bond in the polyester polyurethane resin is preferably 200 to 8,000, more preferably 200 to 5,000, further preferably 300 to 2,000, particularly preferably 400 to 1,500, and most preferably 700 to 1,000. In the polyester polyurethane resin, when there are 40 urethane bonds per molecule and the number average molecular weight is 32,000, the molecular weight per urethane bond is 800 (32,000 / 40=800). When there are X urethane bonds per molecule of the polyester polyurethane resin and the number average molecular weight is Y, the molecular weight per urethane bond in the polyester polyurethane resin is Y / X. In the case of calculation based on the raw material composition, the number of moles of isocyanate groups reacted per 1 mole of the polyester polyol as the raw material of the polyester polyurethane resin (C) can also be regarded as the "number of urethane bonds in the polyester polyurethane resin".

[0058] From the viewpoint of adhesion and conductivity, the acid value of the polyurethane resin (C) (preferably the acid value of a polyester polyurethane resin) is preferably 0 mgKOH / g to 50 mgKOH / g, more preferably 0.1 mgKOH / g to 20 mgKOH / g, further preferably 0.1 mgKOH / g to 5 mgKOH / g, and particularly preferably 1.0 mgKOH / g to 5.0 mgKOH / g. From the viewpoint of heat resistance, the acid value of the polyester polyurethane resin (C) is preferably 20 mgKOH / g or less, particularly preferably 5.0 mgKOH / g or less. The method for measuring the acid value of a resin in the present disclosure is a method of determining the acid value by neutralizing and titrating a sample with a potassium hydroxide benzyl alcohol solution using a phenolphthalein solution as an indicator.

[0059] Among them, from the viewpoints of adhesion, conductivity and heat resistance, the polyester polyurethane resin is preferably a polyester polyurethane resin containing a polyester structure having a number average molecular weight of 1,000 to 50,000, more preferably a polyester polyurethane resin containing a polyester structure having a number average molecular weight of 2,000 to 40,000, further preferably a polyester polyurethane resin containing a polyester structure having a number average molecular weight of 3,000 to 30,000, particularly preferably a polyester polyurethane resin containing a polyester structure having a number average molecular weight of 8,000 to 30,000, and most preferably a polyester polyurethane resin containing a polyester structure having a number average molecular weight of 15,000 to 30,000.

[0060] The adhesive composition of the present disclosure may contain a polyurethane resin (C). The polyurethane resin (C) may be used alone or in combination of two or more. From the viewpoint of soldering heat resistance, adhesion and conductivity, the content of the polyurethane resin (C) (preferably the content of the polyester polyurethane resin) is preferably 1% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, and particularly preferably 15% by mass to 35% by mass relative to the total solid content of the adhesive composition.

[0061] <Conductive filler (D)> From the viewpoint of electrical conductivity and soldering heat resistance, the adhesive composition of the present disclosure preferably further contains a conductive filler (G). The volume resistivity of the conductive filler is preferably less than 1.0×10 11 Ω·cm. As the conductive filler (D), metal particles composed of conductive metals (such as gold, platinum, silver, copper, nickel, etc.) or their alloys can be preferably cited. From the viewpoint of reducing costs, the conductive filler (D) may also be particles that are not particles of a single composition. Particles that are not particles of a single composition (hereinafter also referred to as "covered particles") have a core body and a covering layer attached to the core body. The core body is composed of a metal or a resin. The covering layer is formed of a material with high conductivity. The core body is preferably composed of at least one material selected from the group consisting of nickel, silicon dioxide, copper and a resin, and more preferably composed of a conductive metal or its alloy. The covering layer is preferably a layer composed of a material with excellent conductivity, preferably a layer composed of a conductive metal or a conductive polymer. Examples of conductive metals include gold, platinum, silver, tin, manganese, indium, and alloys thereof. Examples of conductive polymers include polyaniline and polyacetylene. Among them, silver is preferred from the viewpoint of conductivity. Other examples include conductive metal oxides such as indium tin oxide, and carbon black.

[0062] From the viewpoint of cost and conductivity, the ratio of the coating layer covering the particles is preferably 1 to 40 parts by mass, more preferably 5 to 30 parts by mass, based on 100 parts by mass of the core.

[0063] The coated particles are preferably particles in which the core is completely covered by the coating layer. A portion of the core may be exposed. In the case where a portion of the core is exposed, the ratio of the area of ​​the core covered by the coating layer to the surface area of ​​the core is preferably 70% or more from the viewpoint of facilitating the maintenance of conductivity.

[0064] The shape of the conductive filler (D) is not limited as long as the desired conductivity can be obtained. The conductive filler (D) is preferably in the shape of a sphere, flake, leaf, dendrite, plate, needle, rod or grape.

[0065] From the viewpoint of conductivity and storage stability, the average particle size of the conductive filler (D) is preferably 1 μm to 100 μm, more preferably 3 μm to 50 μm, and particularly preferably 4 μm to 15 μm. The average particle size of the filler in this specification is the D50 average particle size in the volume-based particle size distribution obtained by measuring the filler using a laser diffraction and scattering particle size distribution measuring device LS13320 (Beckman-Coulter Co., Ltd.) using a cyclone-dried powder sample module. The D50 average particle size represents the average particle size of the diameter of the particle size with a cumulative value of 50% by volume from the particle side of the volume-based particle size distribution.

[0066] The adhesive composition of the present disclosure preferably further comprises a conductive filler (D). Thus, an adhesive composition having conductivity can be provided. The conductive filler (D) may be used alone or in combination of two or more. From the viewpoints of conductivity, heat resistance and storage stability, the content of the conductive filler (D) is preferably 1 to 500 parts by mass, more preferably 10 to 350 parts by mass, and particularly preferably 10 to 200 parts by mass, relative to 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C) which may be contained as an optional component in the adhesive composition.

[0067] In the present disclosure, “100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B), and the polyester polyurethane resin (C) which may be contained as an optional component in the adhesive composition” means: When the adhesive composition contains the polyester polyurethane resin (C), the total amount of the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C) is 100 parts by mass, When the adhesive composition does not contain the polyester polyurethane resin (C), the total amount of the polyester polyamide resin (A) and the epoxy resin (B) is 100 parts by mass.

[0068] <Imidazole silane compound (E)> From the viewpoint of conductivity and adhesiveness, the adhesive composition of the present disclosure preferably further contains an imidazole silane compound (E). The imidazole silane compound (E) refers to a compound having one or more imidazole ring structures and one or more silane structures. It is estimated that the imidazole silane compound (E) functions as a curing agent for the epoxy resin (B). From the viewpoint of conductivity and adhesiveness, the imidazole silane compound (E) is preferably a compound having one imidazole ring structure and one silyl group. As the imidazole silane compound (E), preferably, from the viewpoint of conductivity and adhesiveness, a compound represented by the following formula (E) or an acid adduct thereof is used.

[0069] [Chemical formula 1]

[0070] In formula (E), R 1 and R 2 Each independently represents a hydrogen atom, a saturated hydrocarbon group, an unsaturated hydrocarbon group or an aryl group, and each of the above groups may have a substituent. 3 and R 4 Each independently represents a hydrogen atom or an alkyl group. 3 At least one of R is an alkyl group, and the alkyl group may have a substituent. n represents an integer of 1 to 3. 5 It represents an alkylene group or a group in which a part of the alkylene group is substituted with at least one of formula (E2) to formula (E5).

[0071] [Chemical formula 2]

[0072] In formula (E2), formula (E3) and formula (E5), R 6 represents a hydrogen atom or a hydroxyl group. 7 represents a hydrogen atom, an alkyl group or an aryl group. 8 and R 9 Each independently represents a hydrogen atom, an alkyl group or an aryl group, and each of the groups may have a substituent. The wavy line portion represents a bonding position with other structures.

[0073] If the adhesive composition contains an imidazole silane compound (E) (particularly a compound represented by the formula (E)), the adhesion to metal (particularly gold-plated copper foil) is improved. This shows that the silane structure and the imidazole ring structure have a high affinity with the metal surface. Therefore, it is presumed that the adhesion is improved by its interaction. In addition, the imidazole ring structure can also react with the epoxy resin (B). Therefore, it is presumed that the adhesion improvement effect can also be maintained in the reflow process described later.

[0074] The imidazole silane compound (E) is preferably a compound having both an imidazole ring structure and an alkoxysilyl group in one molecule. The adhesive composition of the present disclosure further contains an imidazole silane compound (E) having an alkoxysilyl group, so that soldering heat resistance can be further improved. The imidazole ring in the imidazole ring structure may have a substituent (eg, a saturated hydrocarbon group, an unsaturated hydrocarbon group, etc.). In formula (E), R 1 , R 2 , R 3 and R 4 In the case of an alkyl group, the number of carbon atoms is preferably 1 to 3. Examples of the imidazole ring structure constituting the imidazole silane compound (E) include an imidazole ring structure, a 2-alkyl imidazole ring structure, a 2,4-dialkyl imidazole ring structure, and a 4-vinylimidazole ring structure. In the imidazole silane compound (E), the alkoxysilyl group and the imidazole ring structure are preferably bonded via an alkylene group or a group in which a part of the alkylene group is substituted by any one of the formulae (E2) to (E5). R of formula (E) 5 The alkylene group in the above-mentioned group preferably has 1 to 10 carbon atoms, and more preferably has 3 to 7 carbon atoms. The imidazole silane compound (E) can be suitably synthesized by, for example, reacting an imidazole compound with a 3-glycidoxyalkylsilane compound or the like. The imidazole silane compound (E) may be a silanol compound generated by hydrolysis of an alkoxysilyl group, may be a polyorganosiloxane compound generated by a dehydration condensation reaction of a silanol compound, or may be a mixture thereof. Examples of the acid added to the compound represented by formula (E) include acetic acid, lactic acid, salicylic acid, benzoic acid, adipic acid, phthalic acid, citric acid, tartaric acid, maleic acid, trimellitic acid, phosphoric acid, and isocyanuric acid, etc. These can be used alone or in combination of two or more.

[0075] As the imidazole silane compound (E), from the viewpoint of conductivity and adhesiveness, a compound represented by the following formula (E6) or formula (E7) or an acid adduct thereof is more preferable.

[0076] [Chemical formula 3]

[0077] In formula (E6) and formula (E7), R 1 and R 2 Each independently represents a hydrogen atom, a saturated hydrocarbon group, an unsaturated hydrocarbon group or an aryl group, and each of the above groups may have a substituent. 3 and R 4 Each independently represents a hydrogen atom or an alkyl group. 3 At least one of R is an alkyl group, and the alkyl group may have a substituent. n represents an integer of 1 to 3. 5 ' represents an alkylene group. 6 represents a hydrogen atom or a hydroxyl group.

[0078] R in formula (E6) and formula (E7) 5 The number of carbon atoms of the alkylene group in ' is preferably 1-10, more preferably 3-7.

[0079] Examples of the imidazole silane compound (E) include 1-(2-hydroxy-3-trimethoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-tripropoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-tributoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-tributoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)imidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)-2-methylimidazole, 1-(2-hydroxy-3-triethoxysilylpropoxypropyl)-4-methylimidazole, 1-(3-oxo-4-trimethoxysilylpropoxypropyl)imidazole, and 1-(3-trimethoxysilylpropylamino)imidazole.

[0080] Among them, from the viewpoint of good heat resistance and improved solubility in solvents, the compound represented by the formula (E6) or (E7) or its acid adduct is more preferably an acid adduct of the compound represented by the formula (D6).

[0081] The compound represented by the formula (E6) can be suitably obtained by reacting an imidazole compound with a 3-glycidoxypropylsilane compound, or the like. Examples of the imidazole compound include imidazole, 2-alkylimidazole, 2,4-dialkylimidazole, and 4-ethylimidazole. Examples of the 3-glycidoxypropylsilane compound include 3-glycidoxypropyltrialkoxysilane, 3-glycidoxypropyldialkoxyalkylsilane, and 3-glycidoxypropylalkoxydialkylsilane. Among them, the reaction product of imidazole and 3-glycidoxypropyltrimethoxysilane is particularly preferred. The compound represented by the formula (E7) can be suitably obtained by reacting an imidazole compound with 3-methacryloxypropyltrimethoxysilane or the like.

[0082] The adhesive composition of the present disclosure may contain one type of imidazole silane compound (E) alone, or two or more types thereof. From the viewpoint of conductivity and adhesion, the content of the imidazole silane compound (E) is preferably 0.05 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and particularly preferably 1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B), and the polyester polyurethane resin (C) that may be optionally contained in the adhesive composition.

[0083] <Inorganic filler (F)> From the viewpoint of soldering heat resistance and electrical conductivity, the adhesive composition of the present disclosure preferably further contains a non-conductive inorganic filler (F) (hereinafter also simply referred to as "inorganic filler (F)"), and more preferably further contains a non-conductive inorganic filler (F) and a non-conductive organic filler (G) described below. The inorganic filler (F) having no conductivity in the present specification and the organic filler (G) having no conductivity described later are inorganic fillers or organic fillers other than the conductive filler (D) described above.

[0084] The inorganic filler (F) is not particularly limited, and examples thereof include non-conductive inorganic fillers and conductive inorganic fillers. Examples of the non-conductive inorganic filler include calcium carbonate particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, talc particles, and silicon dioxide particles. Examples of the conductive inorganic filler include carbon black particles. Among them, from the viewpoint of the conductivity of the obtained cured product in the initial stage, after welding, after long-term reliability test and after thermal cycle test, the inorganic filler (F) is preferably at least one particle selected from the group consisting of talc particles and silica particles, and more preferably talc particles.

[0085] The average particle size of the inorganic filler (F) is not particularly limited, but is preferably 0.001 μm to 50 μm, more preferably 0.005 μm to 30 μm, and particularly preferably 0.01 μm to 10 μm from the viewpoint of the conductivity, coating properties, and coating thickness adjustability of the resulting cured product in the initial stage, after welding, after long-term reliability testing, and after thermal cycle testing.

[0086] The inorganic filler (F) may be used alone or in combination of two or more. From the viewpoint of soldering heat resistance and electrical conductivity, the inorganic filler (F) is preferably used in combination of two or more, more preferably two. From the viewpoints of adhesion, conductivity and curing properties, the content of the inorganic filler (F) is preferably 0.1 to 50 parts by mass, more preferably 0.5 to 20 parts by mass, and particularly preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C) that may be optionally contained in the adhesive composition.

[0087] <Organic filler (G)> From the viewpoints of soldering heat resistance, electrical conductivity, and moisture-heat resistance, the adhesive composition of the present disclosure preferably contains an organic filler (G) that is not electrically conductive (hereinafter also simply referred to as “organic filler (G)”). Examples of the organic filler (G) include (meth)acrylic resin particles, polybutadiene particles, nylon particles, polyolefin particles, polyester particles, polycarbonate particles, polyvinyl alcohol particles, polyvinyl ether particles, polyvinyl butyral particles, silicone rubber particles, polyurethane particles, phenolic resin particles, and polytetrafluoroethylene particles. The organic filler can improve the compatibility of the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C) which may be contained arbitrarily when dissolved in the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C). In addition, from the viewpoint of further improving the compatibility and liquid stability of these resins, silicone particles, polybutadiene particles, (meth) acrylic resin particles or polyurethane particles are particularly preferred.

[0088] The average particle size of the organic filler (G) is not particularly limited, but is preferably 0.5 μm to 50 μm, more preferably 1 μm to 30 μm, from the viewpoint of coating properties and coating thickness adjustability.

[0089] The adhesive composition of the present disclosure may contain an organic filler (G). The organic filler (G) may be used alone or in combination of two or more. From the viewpoints of adhesion, conductivity and curing properties, the content of the organic filler (G) is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and particularly preferably 10 to 20 parts by mass, relative to 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B) and the polyester polyurethane resin (C) that may be optionally contained in the adhesive composition.

[0090] The resin composition of the present disclosure may contain additives other than the above-mentioned components to the extent that the functions of the adhesive composition are not affected. Examples of other additives include other thermoplastic resins other than those mentioned above, tackifiers, flame retardants, curing agents, curing accelerators, coupling agents, heat aging inhibitors, leveling agents, defoaming agents, and solvents.

[0091] Examples of the other thermoplastic resins include phenoxy resins, polyester resins, polyamide resins, polycarbonate resins, polyphenylene ether resins, polyurethane resins, polyacetal resins, polyethylene resins, polypropylene resins, and polyethylene resins. These thermoplastic resins may be used alone or in combination of two or more.

[0092] Examples of the tackifier include coumarone-indene resin, terpene resin, terpene-phenolic resin, rosin resin, p-tert-butylphenol-acetylene resin, phenol-formaldehyde resin, xylene-formaldehyde resin, petroleum hydrocarbon resin, hydrogenated hydrocarbon resin, and turpentine resin. These tackifiers may be used alone or in combination of two or more.

[0093] The flame retardant may be any one of an organic flame retardant and an inorganic flame retardant. Examples of the organic flame retardant include a phosphorus flame retardant, a nitrogen flame retardant, and a silicon flame retardant. Examples of the phosphorus flame retardant include melamine phosphate, melamine polyphosphate, guanidine phosphate, guanidine polyphosphate, ammonium phosphate, ammonium polyphosphate, ammonium phosphate, ammonium polyphosphate, phosphoric acid carbamate, polyphosphoric acid carbamate, aluminum tridiethylphosphonate, aluminum trimethylethylphosphinate, aluminum tridiphenylphosphinate, zinc bisdiethylphosphinate, zinc bismethylethylphosphinate, zinc bisdiphenylphosphinate, bisdiethylphosphinate titanium oxide, titanium tetradiethylphosphinate, titanium bismethylethylphosphinate, titanium tetramethylethylphosphinate, titanium bisdiphenylphosphinate, and titanium tetradiphenylphosphinate. Examples of the nitrogen-based flame retardant include triazine compounds such as melamine, melam, and melamine cyanurate, cyanuric acid compounds, isocyanuric acid compounds, triazole compounds, tetrazole compounds, diazo compounds, and urea. Examples of the silicon-based flame retardant include organic silicon compounds and silane compounds. Examples of the inorganic flame retardant include metal hydroxides, metal oxides, zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, zinc borate, and hydrated glass. Examples of the metal hydroxide include aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, barium hydroxide, and calcium hydroxide. Examples of the metal oxide include tin oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, molybdenum oxide, and nickel oxide. These flame retardants may be used alone or in combination of two or more.

[0094] The curing agent is a component for forming a crosslinked structure by reacting with the epoxy resin (B), and examples of the curing agent include acid curing agents, alkaline active hydrogen curing agents, polythiol curing agents, novolac resin curing agents, urea resin curing agents, and melamine resin curing agents. Examples of the acid curing agent include amine curing agents (such as aliphatic diamines, aliphatic polyamines, cycloaliphatic diamines, and aromatic diamines), polyamide amine curing agents, aliphatic polycarboxylic acids, alicyclic polycarboxylic acids, aromatic polycarboxylic acids, and anhydrides thereof. Examples of the alkaline active hydrogen curing agent include dicyandiamide and organic acid dihydrazide. These curing agents may be used alone or in combination of two or more.

[0095] Examples of the aliphatic diamine curing agent include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, polymethylenediamine, polyetherdiamine, 2,5-dimethylhexamethylenediamine, and trimethylhexamethylenediamine.

[0096] Examples of the aliphatic polyamine curing agent include diethylenetriamine, iminobis(hexamethylene)triamine, trihexanetetramine, tetraethylenepentamine, aminoethylethanolamine, tri(methylamino)hexane, dimethylaminopropylamine, diethylaminopropylamine, and methyliminobispropylamine.

[0097] Examples of the cyclic aliphatic diamine curing agent include menthylene diamine, isophorone diamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, bis(aminomethyl)cyclohexane, N-ethylaminopiperazine, 3,9-bis(3-aminopropyl)2,4,8,10-tetraoxaspiro[5.5]undecane, and hydrogenated meta-xylylenediamine.

[0098] Examples of the aromatic diamine curing agent include meta-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, diaminodiethyldiphenylmethane, and meta-xylylenediamine.

[0099] Examples of the aliphatic polycarboxylic acid-based curing agent and the acid anhydride-based curing agent include succinic acid, adipic acid, dodecenylsuccinic anhydride, polyadipic anhydride, polyazelaic anhydride, and polysebacic anhydride.

[0100] Examples of the alicyclic polycarboxylic acid curing agent and the acid anhydride curing agent include methyltetrahydrophthalic acid, methylhexahydrophthalic acid, methylnadic acid, hexahydrophthalic acid, tetrahydrophthalic acid, trialkyltetrahydrophthalic acid, methylcyclodicarboxylic acid, and anhydrides thereof.

[0101] Examples of the aromatic polycarboxylic acid curing agent and the acid anhydride curing agent include phthalic acid, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, ethylene glycol diol trimellitic acid, glycerol trimellitic acid, and anhydrides thereof.

[0102] Examples of the polythiol curing agent include mercapto-modified epoxy resins and mercaptopropionic acid esters.

[0103] Examples of the novolac curing agent include phenol novolac curing agents and cresol novolac curing agents.

[0104] When the adhesive composition of the present disclosure contains the curing agent, the functional group equivalent of the curing agent content is preferably 0.2 to 2.5 molar equivalents, more preferably 0.4 to 2.0 molar equivalents, relative to 1 molar equivalent of epoxy groups of the epoxy resin (B), from the viewpoint of adhesiveness and heat resistance.

[0105] The curing accelerator is a component used to accelerate the reaction of the epoxy resin (B), and a tertiary amine curing accelerator, a tertiary amine salt curing accelerator, an imidazole curing accelerator, or the like can be used. These curing accelerators may be used alone or in combination of two or more.

[0106] Examples of the tertiary amine curing accelerator include benzyldimethylamine, 2-tris(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, triethanolamine, N,N′-dimethylpiperazine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]undecene.

[0107] Examples of the tertiary amine salt curing accelerator include formate, octanoate, p-toluenesulfonate, phthalate, phenolate or phenol novolac resin salt of 1,8-diazabicyclo[5.4.0]undecene, formate, octanoate, p-toluenesulfonate, phthalate, phenolate or phenol novolac resin salt of 1,5-diazabicyclo[4.3.0]nonene, and the like.

[0108] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-methyl-4-ethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine. -Undecyl imidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc.

[0109] When the adhesive composition of the present disclosure contains a curing accelerator, the content of the curing accelerator is preferably 1 to 10 parts by mass, more preferably 2 to 5 parts by mass, based on 100 parts by mass of the epoxy resin (B), from the viewpoint of adhesiveness and heat resistance.

[0110] Examples of the coupling agent include silane-based coupling agents, titanate-based coupling agents, aluminate-based coupling agents, and zirconium-based coupling agents. Examples of the silane coupling agent include vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-phenylvinyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, and imidazolesilane. These may be used alone or in combination of two or more.

[0111] Examples of the heat aging inhibitor include phenolic antioxidants, sulfur antioxidants, and phosphorus antioxidants. Examples of the phenolic antioxidant include 2,6-di-tert-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, and tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane. Examples of the sulfur-based antioxidant include dilauryl-3,3'-dithiopropionate and dimyristyl-3,3'-dithiopropionate. Examples of the phosphorus antioxidant include trisnonylphenyl phosphite and tris(2,4-di-tert-butylphenyl) phosphite. These may be used alone or in combination of two or more.

[0112] The adhesive composition of the present disclosure can be prepared by mixing a polyester polyamide resin (A), an epoxy resin (B), and other components as necessary. Since the adhesive composition of the present disclosure is preferably used in the state of a solution or a dispersion, it preferably contains a solvent. Examples of the solvent include alcohols, ketones, aromatic hydrocarbons, esters, and aliphatic hydrocarbons. Examples of the alcohol include methanol, ethanol, isopropanol, n-propanol, isobutanol, n-butanol, benzyl alcohol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and diacetone alcohol. Examples of ketones include acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and isophorone. Examples of the aromatic hydrocarbons include toluene, xylene, ethylbenzene, and mesitylene. Examples of the esters include methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate. Examples of the aliphatic hydrocarbons include hexane, heptane, cyclohexane, and methylcyclohexane. The polyester polyamide resin (A) is easily dissolved in a protic solvent, and among them, a solvent containing an alcohol is preferred. These solvents may be used alone or in combination of two or more. If the adhesive composition of the present disclosure is a solution or dispersion containing a solvent, coating on an adherend and forming an adhesive composition layer can be smoothly performed, and an adhesive composition layer of a desired thickness can be easily obtained.

[0113] When the adhesive composition of the present disclosure contains a solvent, the solid content concentration of the solvent is preferably 3% by mass to 80% by mass, and more preferably 10% by mass to 50% by mass, from the viewpoint of workability including coating film formability.

[0114] The preferred adherend material formed by the adhesive composition of the present invention can include polymer materials, metal materials, etc. As polymer materials, for example, polyimide resins, polyetheretherketone resins, polyphenylene sulfide resins, aromatic polyamide resins, and liquid crystal polymers can be mentioned. As metal materials, for example, copper, aluminum, and stainless steel can be mentioned. The shape of the adherend is not particularly limited. By bonding two components as adherends to each other using the adhesive composition of the present invention, an integrated composite can be manufactured. The materials of the two components can be the same or different. By using the adhesive composition of the present invention, a product (such as a covering film, a bonding sheet, etc.) having an adhesive composition layer can be manufactured, and the adhesive composition layer has adhesion.

[0115] In the adhesive composition of the present disclosure, from the viewpoints of soldering heat resistance, adhesiveness, and moisture resistance, the water absorption of a cured product obtained by curing the adhesive composition of the present disclosure when immersed in water at 23° C. for 24 hours is preferably 4% or less, more preferably 3% or less, and particularly preferably 2.7% or less. The lower limit of the water absorption is 0%. The water absorption of the cured product of the adhesive composition in the present disclosure is calculated as follows. A sheet, an adhesive composition layer and a sheet are overlapped in sequence to obtain a superposition body. The superposition body is heat-pressed at 150°C and 3MPa for 5 minutes, and then heat-cured at 160°C for 2 hours to prepare a cured product of the adhesive composition with a thickness of 100μm. Thus, a laminate is obtained. The laminate is formed by stacking a sheet, a cured product of the adhesive composition and a sheet in sequence. According to JIS K 7114 (2001), the water absorption of the laminate when immersed in water at 23°C for 24 hours is taken as the water absorption of the cured product of the adhesive composition.

[0116] (Laminate with adhesive composition layer and laminate) The laminate with adhesive composition layer disclosed in the present invention is a laminate using the adhesive composition disclosed in the present invention. The laminate with adhesive composition layer disclosed in the present invention comprises an adhesive composition layer and a substrate film in contact with at least one surface of the adhesive composition layer. The adhesive composition layer is an adhesive composition layer composed of an uncured material of the adhesive composition disclosed in the present invention, an adhesive composition layer in a B-stage state formed by partially curing the adhesive composition, or a cured layer formed by curing the adhesive composition. In the present disclosure, “uncured material of the adhesive composition” means an uncured state of the adhesive composition. In the present disclosure, “the adhesive composition layer is in a B-stage state” means a semi-cured state in which a part of the adhesive composition layer begins to cure. In other words, the B-stage state is a state in which curing of the adhesive composition layer is further advanced by heating or the like. When an adhesive composition containing a solvent is used, the adhesive composition layer composed of an uncured material of the adhesive composition of the present disclosure is preferably a layer obtained by removing at least a part of the solvent from the adhesive composition of the present disclosure.

[0117] The laminate with an adhesive composition layer of the present disclosure and the laminate of the present disclosure preferably have a substrate, and more preferably have a layer composed of the adhesive composition of the present disclosure on a substrate. The substrate is not particularly limited, and a known substrate can be used. As the substrate, a film-like substrate (substrate film) is preferred. The substrate film is preferably a resin film, more preferably a polyimide film or an aramid film, and particularly preferably a polyimide film. The polyimide film or aramid film is not particularly limited as long as it has electrical insulation properties, and examples thereof include films consisting only of polyimide resin or aramid resin, films containing polyimide resin or aramid resin and additives, etc. The side on which the adhesive composition layer is formed may be subjected to surface treatment. The thickness of the substrate is not particularly limited, but is preferably 3 μm to 125 μm. The thickness of the adhesive composition layer is preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm.

[0118] As a method for manufacturing a laminate with an adhesive composition layer of the present disclosure, for example, there can be mentioned a method of applying the adhesive composition of the present disclosure containing a solvent on the surface of a substrate film (e.g., a polyimide film, etc.) to form an adhesive composition layer, and then removing at least a portion of the solvent from the adhesive composition layer (hereinafter also referred to as "the first method"), etc. By the first method, a laminate having a B-stage adhesive composition layer can be manufactured. The drying temperature when removing the solvent is preferably 40°C to 250°C, more preferably 70°C to 170°C. Drying is performed by passing the laminate coated with the adhesive composition through an oven, in which hot air drying, far infrared heating, high-frequency induction heating, etc. are performed. The laminate with an adhesive composition layer of the present disclosure may further include a release film for storage or the like on the surface of the adhesive composition layer as necessary. Examples of the release film include polyethylene terephthalate films, polyethylene films, polypropylene films, silicone release-treated papers, polyolefin resin-coated papers, polymethylpentene (TPX) films, fluorine-based resin films, etc. The release film may be a known one.

[0119] The thickness of the adhesive composition layer in the B-stage state is preferably 5 μm to 100 μm, more preferably 5 μm to 70 μm, further preferably 5 μm to 50 μm, and particularly preferably 10 μm to 40 μm. The thickness of the substrate film and the adhesive composition layer is selected according to the application, but the substrate film may be thinner in order to improve the electrical properties. The preferred thickness of the substrate film is the same as the preferred thickness of the substrate described above. In the laminate with an adhesive composition layer of the present disclosure, the ratio (A / B) of the thickness of the adhesive composition layer (A) to the thickness of the substrate film (B) is preferably 1 to 10, more preferably 1 to 5. Furthermore, the thickness of the adhesive composition layer is preferably thicker than the thickness of the substrate film.

[0120] As a method for manufacturing the laminate of the present invention, for example, after applying the adhesive composition of the present invention containing a solvent on the surface of the substrate film, it is dried in the same manner as the laminate with the adhesive composition layer of the present invention, and then the surface of the formed adhesive composition layer is brought into contact with the adherend surface and laminated (for example, thermally laminated at 80°C to 150°C). Thus, a laminate (substrate film / adhesive composition layer / adhesive) can be obtained. The laminate (substrate film / adhesive composition layer / adhesive) is formed by sequentially laminating a substrate film, an adhesive composition layer, and an adherend. Next, a method of heat-pressing the laminate (substrate film / adhesive composition layer / adhesive) and then curing the adhesive composition layer by post-curing to form a cured layer can be preferably cited. The conditions for heat compression bonding are not particularly limited as long as compression bonding is possible, but preferably 150°C to 200°C and a pressure of 1 MPa to 3 MPa for 1 minute to 60 minutes. The conditions for post-curing are not particularly limited, but preferably 100°C to 200°C and 30 minutes to 4 hours. The thickness of the cured layer is preferably 5 μm to 100 μm, more preferably 5 μm to 70 μm, further preferably 5 μm to 50 μm, and particularly preferably 10 μm to 40 μm. The adherend is not particularly limited, and examples thereof include the adherends described above. Among them, a metal adherend is preferred, a copper foil or a plated copper foil is more preferred, and a gold-plated copper foil is particularly preferred. The shape and size of the adherend are not particularly limited, and a known adherend can be used.

[0121] The laminated body of the present disclosure includes a cured layer formed by curing the adhesive composition of the present disclosure. As one embodiment of the laminated body of the present disclosure, a flexible copper-clad laminate can be cited. That is, the flexible copper-clad laminate of the present disclosure has a cured layer formed by curing the adhesive composition of the present disclosure. The flexible copper-clad laminate of the present disclosure is preferably a laminate having a polyimide film or an aramid film, a cured layer formed by curing the adhesive composition of the present disclosure, and a copper foil. In the flexible copper-clad laminate of the present invention, the cured layer and the copper foil may be formed on both sides of the polyimide film or the aramid film. The adhesive composition of the present invention has excellent adhesion to articles containing copper. Therefore, the flexible copper-clad laminate of the present invention has excellent stability as an integrated object.

[0122] The structure of the polyimide film or the aramid film is the same as that of the polyimide film or the aramid film in the aforementioned cover film of the present disclosure. The thickness of the cured layer is preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm. The copper foil is not particularly limited, and examples thereof include electrolytic copper foil and rolled copper foil. The copper foil may be plated with a known metal (for example, gold, silver, etc.) or an alloy.

[0123] As one embodiment of the laminate with an adhesive composition layer of the present disclosure, there can be mentioned a bonding film, an electromagnetic wave shielding film, a cover film, and the like which will be described later.

[0124] -Jointing film- The bonding film of the present disclosure uses the adhesive composition of the present disclosure. The bonding film of the present disclosure preferably comprises a B-stage adhesive composition layer obtained by partially curing the adhesive composition of the present disclosure, and a release film in contact with at least one surface of the adhesive composition layer. The bonding film of the present disclosure is also one embodiment of the laminate with the adhesive composition layer of the present disclosure described above. The bonding film of the present disclosure may be a mode in which an adhesive composition layer is provided between two release films. As the release film, the above-mentioned known release films can be used. The thickness of the releasable film is preferably 20 μm to 100 μm. The thickness of the adhesive composition layer is preferably 5 μm to 100 μm, more preferably 10 μm to 60 μm.

[0125] As a method for producing the joining sheet of the present disclosure, for example, a method of applying the adhesive composition of the present disclosure containing a solvent on the surface of a release film and then drying it in the same manner as in the case of the laminate with an adhesive composition layer of the present disclosure described above can be preferably mentioned.

[0126] -Electromagnetic wave shielding film- The electromagnetic wave shielding film disclosed in the present invention uses the adhesive composition disclosed in the present invention. The electromagnetic wave shielding film disclosed in the present invention preferably has an adhesive composition layer. The adhesive composition layer is an adhesive composition layer composed of an uncured material of the adhesive composition disclosed in the present invention, an adhesive composition layer in a B-stage state formed by curing a portion of the adhesive composition, or a cured layer formed by curing the adhesive composition. The electromagnetic wave shielding film disclosed in the present invention is more preferably a cured layer formed by curing the adhesive composition. The electromagnetic wave shielding film of the present disclosure preferably has the adhesive composition layer and a protective layer. The protective layer is not particularly limited as long as it is a layer composed of an insulating adhesive composition, and any known layer may be used. The protective layer may use the resin component used in the adhesive composition of the present disclosure. The protective layer may be formed of two or more layers having different compositions or hardnesses. The protective layer may contain a curing accelerator, a tackifier, an antioxidant, a pigment, a dye, a plasticizer, an ultraviolet absorber, a defoaming agent, a leveling agent, a filler, a flame retardant, a viscosity modifier, an anti-blocking agent, and the like as required.

[0127] The thickness of the adhesive composition layer in the electromagnetic wave shielding film of the present disclosure is not particularly limited, but is preferably 3 μm to 30 μm from the viewpoint of electrical conductivity and connectivity with a ground circuit.

[0128] Next, a specific embodiment of the method for producing the electromagnetic shielding film of the present disclosure will be described. Examples of the method for producing the electromagnetic wave shielding film of the present disclosure include a method in which an adhesive composition for a protective layer is applied to one surface of a releasable film and dried to form a protective layer, and an adhesive composition of the present disclosure is applied to the protective layer and dried to form an adhesive composition layer. According to the exemplified production method, an electromagnetic wave shielding film in which an adhesive composition layer, a protective layer, and a peelable film are laminated in this order can be obtained.

[0129] The method for providing the adhesive composition layer and the protective layer may be a known coating method. Examples of the method for providing the adhesive composition layer and the protective layer include gravure coating, kiss coating, die coating, lip coating, comma coating, blade coating, roll coating, knife coating, spray coating, rod coating, spin coating, dip coating, and the like.

[0130] The electromagnetic wave shielding film disclosed in the present invention can be bonded to a printed circuit board by, for example, hot pressing. The adhesive composition layer is softened by heating and flows into a grounding portion provided on the printed circuit board by pressurization. Thus, the grounding circuit is electrically connected to the conductive adhesive. As a result, the shielding effect is improved. Example

[0131] Hereinafter, the present disclosure will be specifically described based on Examples. The present disclosure is not limited to these Examples. Hereinafter, unless otherwise specified, "parts" and "%" represent "parts by mass" and "mass %", respectively.

[0132] <<Raw materials used>> 1. Polyester polyamide resin (A) <Preparation of polyester polyamide resin (a1)> In a flask equipped with a stirrer, a reflux dehydration device and a distillation tube, 7 parts by mass of dimer acid, 406 parts by mass of azelaic acid, 364 parts by mass of isophorone diamine and 120 parts by mass of distilled water were added. The temperature was raised to 120°C, and after the water was distilled off, the temperature was raised to 240°C at a rate of 20°C / hour and maintained for 1 hour. 200 parts by mass of azelaic acid, 125 parts by mass of neopentyl glycol and 2.1 parts by mass of tetrabutoxy titanate as an esterification catalyst were further added to the reaction product, and the temperature was lowered to 150°C. The temperature was raised to 220°C again, and the reaction was continued until the amine value reached 7.6 mgKOH / g to obtain a polyester polyamide resin (a1).

[0133] <Production of polyester polyamide resin (a2)> A polyester polyamide resin (a2) was obtained in the same manner as in the preparation of the polyester polyamide resin (a1) except that the reaction was continued until the amine value reached 4.3 mgKOH / g.

[0134] 2. Polyamide resin without polyester (A') <Production of Polyamide Resin (a3) ​​Not Containing Polyester> In a flask equipped with a stirrer, a reflux dehydration device and a distillation tube, 65 parts by mass of azelaic acid, 190 parts by mass of dodecanedioic acid, 100 parts by mass of piperazine and 120 parts by mass of distilled water were added. The temperature was raised to 120°C to distill off the water, and then the temperature was raised to 240°C at a rate of 20°C / hour, and the reaction was continued for 3 hours to obtain a polyamide resin (a3). The amine value of the resin was 4.5 mgKOH / g.

[0135] 3. Epoxy resin (B) Epoxy resin (b1): Trisphenol methane type epoxy resin "jER 1032H60" (trade name) manufactured by Mitsubishi Chemical Corporation Epoxy resin (b2): Bisphenol A novolac type epoxy resin "EPICLON N-865" (trade name) manufactured by DIC Corporation Epoxy resin (b3): ​​Bisphenol A type epoxy resin "jER 1055" (trade name) manufactured by Mitsubishi Chemical Corporation

[0136] 4. Polyurethane resin (C) <Production of polyurethane resin (c1)> In a flask equipped with a stirrer, a reflux dehydration device and a distillation tube, 600 parts by mass of "PES-360HVXM30" (Aron Melt (registered trademark) PES-360HVXM30 manufactured by Toagosei Co., Ltd., number average molecular weight: 20,000, glass transition point: 65°C), 100 parts by mass of toluene and 20 parts by mass of neopentyl glycol were added. The temperature was raised to 120°C, and after distilling off 100 parts by mass of the aqueous solvent, the temperature was lowered to 105°C, and 0.4 parts by mass of 2,2-dimethylolpropionic acid was added to dissolve it. Then, 34 parts by mass of hexamethylene diisocyanate was added, and 0.2 parts by mass of dibutyltin dilaurate was added after 30 minutes. After continuing the reaction for 6 hours, it was diluted with toluene / 2-propanol to obtain a solution of a polyester polyurethane resin (c1) with a solid content concentration adjusted to 30%. The polyester polyurethane resin (c1) had a number average molecular weight of 36,000, a weight average molecular weight of 140,000, and an acid value of 2 mgKOH / g.

[0137] <Production of polyurethane resin (c2)> In a flask equipped with a stirrer, a reflux dehydration device and a distillation tube, 600 parts by mass of "PES-360HVXM30", 100 parts by mass of toluene, and 30 parts by mass of 2-butyl-2-ethyl-1,3-propanediol were added. The temperature was raised to 120°C, and after distilling off 100 parts by mass of the aqueous solvent, the temperature was lowered to 105°C, and 0.4 parts by mass of 2,2-bis(hydroxymethyl)propionic acid was added and dissolved. Then, 42 parts by mass of norbornane diisocyanate (NBDI) was added, and 0.2 parts by mass of dibutyltin dilaurate was added after 30 minutes. After continuing the reaction until the specified molecular weight was reached, it was diluted with toluene / 2-propanol to obtain a solution of a polyester polyurethane resin (c2) adjusted to a solid content concentration of 30%. The number average molecular weight of the polyester polyurethane resin (c2) was 35,000, the weight average molecular weight was 120,000, and the acid value was 2 mgKOH / g.

[0138] 5. Conductive filler (D) Copper powder "FCC-115A" (trade name) manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.

[0139] 6. Imidazole silane compound (E) 1-(2-Hydroxy-3-trimethoxysilylpropoxypropyl)imidazole

[0140] 6. Non-conductive inorganic filler (F) Inorganic filler (f1): "R972" manufactured by AEROSIL Co., Ltd. of Japan (trade name; average particle diameter 16 nm, silica particles) Inorganic filler (f2): Talc "SG-95" manufactured by Nippon Talc Co., Ltd. (trade name; average particle size 2.5 μm, talc particles)

[0141] 7. Non-conductive organic fillers (G) Organic filler (g1): Acrylate beads "J-4P" manufactured by Negami Industries Co., Ltd. (trade name; average particle diameter 2.2 μm, acrylic resin particles) Organic filler (g2): Urethane beads "TK-800T" manufactured by Negami Industries Co., Ltd. (trade name; average particle size 8 μm, polyurethane resin particles)

[0142] 8. Flame retardants Clariant phosphinate metal salt "Exolit OP935" (trade name)

[0143] 9. Solvent A mixed solvent consisting of toluene, methyl isobutyl ketone and 2-propanol (mass ratio = 100:20:20)

[0144] (Examples 1 to 16 and Comparative Examples 1 to 4) In a flask with a stirring device, the above raw materials are added in the proportion shown in Table 1, and stirred for 6 hours under heating at 60°C, so that the polyester polyamide resin (A) or the polyester-free polyamide resin (A'), epoxy resin (B), polyurethane resin (C), imidazole silane compound (E) and curing accelerator are dissolved in the solvent, and the conductive filler (D), inorganic filler (F), organic filler (G) and flame retardant are dispersed, thereby manufacturing a liquid adhesive composition. Then, using all these liquid adhesive compositions, cover films, bonding sheets, and bonding test pieces A and B are made, and the following (i) to (x) are evaluated. The evaluation results are shown in Table 1.

[0145] (1) Production of covering film The liquid adhesive composition was roll-coated on the surface of a polyimide film having a thickness of 25 μm so as to have a thickness of 15 μm after drying, and dried at 120° C. for 2 minutes to obtain a cover film having an adhesive layer.

[0146] (2) Preparation of Adhesion Test Specimen A Prepare a rolled copper foil with a thickness of 35 μm manufactured by Futian Metal Foil Powder Industry Co., Ltd. The mirror surface is overlapped in contact with the adhesive layer of the above-mentioned covering film, and laminated under the conditions of 150°C, 0.3MPa, and 1m / min to obtain a laminate (polyimide film / adhesive layer / copper foil). The obtained laminate (polyimide film / adhesive layer / copper foil) is formed by laminating a polyimide film, an adhesive layer, and a copper foil in sequence. After the obtained laminate (polyimide film / adhesive layer / copper foil) is heated and pressed at 150°C and 3MPa for 5 minutes, it is further post-cured in an oven at 160°C for 2 hours. Thus, an adhesive test piece A is obtained.

[0147] (3) Fabrication of bonding sheets A 35 μm thick release PET film was prepared. A mixture of a liquid adhesive composition and copper powder "FCC-115A" manufactured by Fukuda Metal Foil Powder Industry Co., Ltd. was prepared so as to be 15% by mass of the total solid content resin. The above mixture was roll-coated on the surface of the release PET film in a manner such that the thickness after drying was 25 μm, and dried at 140° C. for 2 minutes to obtain a bonding sheet having an adhesive layer.

[0148] (4) Preparation of Adhesion Test Specimen B Prepare a flexible printed circuit board. The flexible printed circuit board has a nickel-plated SUS304 board (thickness: 300 μm), a polyimide film (thickness: 25 μm), a circuit pattern (material: copper), and a cover film (thickness: 37.5 μm). The SUS304 board, the polyimide film, and the circuit pattern are stacked in sequence. The cover film is stacked on the circuit pattern. The cover film has a through hole with a diameter of 1 mm. First, the nickel-plated surface of the SUS304 plate was placed in contact with the adhesive layer of the above-mentioned bonding sheet, and laminated under the conditions of 150°C, 0.3 MPa, and 1 m / min to obtain a laminate (SUS plate / adhesive layer / release PET film). The laminate (SUS plate / adhesive layer / release PET film) was formed by laminating the SUS304 plate, the adhesive layer, and the release PET film in this order. Then, the release PET film was peeled off from the laminate (SUS plate / adhesive layer / release PET film), and a flexible printed wiring board (a wiring board having a copper foil circuit formed on a polyimide film having a thickness of 25 μm, and a cover film having a thickness of 37.5 μm and a through hole having a diameter of 1 mm laminated on the copper foil circuit) was heat-pressed for 5 minutes under the conditions of 150°C and 3 MPa, and then post-cured in an oven at 160°C for 2 hours. Thus, an adhesion test piece B (SUS plate / adhesive layer / flexible printed wiring board) was prepared. The adhesion test piece B was obtained by laminating the SUS plate, the adhesive layer, and the flexible printed wiring board in this order.

[0149] (i) Amine value of polyester polyamide resin (A) etc. The amine value of the resin was calculated by potentiometric titration in accordance with JIS K 7237 (1995).

[0150] (ii) Water absorption of cured product The bonding sheets were overlapped, heat-pressed for 5 minutes at 150°C and 3 MPa, and then heat-cured at 160°C for 2 hours to produce a 100 μm thick adhesive cured product. The water absorption of the adhesive cured product when immersed in water at 23°C for 24 hours was calculated in accordance with JIS K 7114 (2001). The measurement results are shown in Table 1.

[0151] (iii) Peel adhesion strength In order to evaluate the adhesion, the 180° peeling strength (N / cm) when the copper foil of each adhesive test piece A was peeled off from the polyimide film was measured according to JIS C 6481 "Test methods for copper-clad laminates for printed wiring boards" at a temperature of 23°C and a tensile speed of 50 mm / min. The width of the adhesive test piece during the measurement was 1.0 cm. The measurement results are shown in Table 1. In Table 1, the item "peel strength" is indicated as "initial" of peel strength. Samples with a measured value of peel strength of 5.0 N / cm or more are indicated as "A". Samples with a measured value of peel strength of 3.5 N / cm or more and less than 5.0 N / cm are indicated as "B". Samples with a measured value of peel strength of less than 3.5 N / cm are indicated as "C".

[0152] (iv) Peel strength after long-term moisture and heat test (long-term moisture and heat resistance) Each adhesive test piece A was stored at 85°C and 85% RH for 1,000 hours, and the 180° peeling strength (N / mm) of each adhesive test piece A after storage was measured when the copper foil was peeled off from the polyimide film at a temperature of 23°C and a tensile speed of 50 mm / min in accordance with JIS C 6481 "Test methods for copper-clad laminates for printed wiring boards". The width of the adhesive test piece during the measurement was 1.0 cm. The measurement results are shown in Table 1. In Table 1, the item "Peel strength after long-term moisture and heat test (long-term moisture and heat resistance)" is expressed as "After 85°C / 85%RH1000hr test" of peel strength. The case where the measured value of peel strength is 5.0N / cm or more is expressed as "A". The case where the measured value of peel strength is 3.5N / cm or more and less than 5.0N / cm is expressed as "B". The case where the measured value of peel strength is less than 3.5N / cm is expressed as "C". The allowable evaluation result of peel strength (long-term moisture and heat resistance) after long-term moisture and heat test is "A" or "B".

[0153] (v) Soldering heat resistance (appearance during welding, peel adhesion strength after welding) The test was performed under the following conditions in accordance with JIS C 6481 (1996). Absolute dry soldering test: According to JIS C 6481 (1996), after pretreatment at 105±2°C, the polyimide film was placed facing upward and floated in a solder bath at 260°C for 60 seconds. Normal humidity soldering test: According to JIS C 6481 (1996), after pretreatment at 105±2°C, place under normal humidity (23±2°C, 50-60% RH) for 24 hours, then float in a 260°C solder bath with the polyimide film facing up for 60 seconds. The adhesive test pieces A after each welding test were visually evaluated for the presence or absence of abnormal appearance such as swelling and peeling of the adhesive layer. In Table 1, the item "Appearance during welding" is indicated as "After the normal wet welding test" of appearance. The case where no abnormal appearance such as micropores, swelling and peeling was observed was indicated as "A". The case where micropores were slightly observed was indicated as "B". The case where abnormal appearance such as swelling and peeling was observed was indicated as "C".

[0154] In addition, for the adhesive test piece A after the normal wet soldering test, the 180° peeling strength (N / cm) when the polyimide film is peeled off from the gold-plated copper foil is measured at 23°C according to JIS C 6481. The width of the adhesive test piece during the measurement is 10 mm, and the tensile speed is 50 mm / min. The width of the adhesive test piece during the measurement is 10 mm. The measurement results are shown in Table 1. In Table 1, the item "peel strength after welding" is indicated as "after normal wet welding test" of peel strength. The case where the measured value of peel strength is 5.0 N / cm or more is indicated as "A". The case where the measured value of peel strength is 3.5 N / cm or more and less than 5.0 N / cm is indicated as "B". The case where the measured value of peel strength is less than 3.5 N / cm is indicated as "C". The acceptable result of peel strength after welding is "A" or "B".

[0155] (vi) Electrical conductivity (initial, connection resistance) The connection resistance between the SUS board of the bonding test piece B (SUS board / adhesive layer / flexible printed wiring board) and the copper foil circuit of the flexible printed wiring board was measured using a resistance measuring device. In Table 1, the item "Conductivity (initial, connection resistance)" is indicated as "initial" of conductivity. The case where the measured value of the connection resistance value is less than 0.3Ω is indicated as "A". The case where the measured value of the connection resistance value is greater than 0.3Ω and less than 1.0Ω is indicated as "B". The case where the measured value of the connection resistance value is greater than 1.0Ω is indicated as "C".

[0156] (vii) Electrical conductivity after long-term damp heat test The bonding test piece B was placed in a constant temperature and humidity chamber at 85°C and 85% RH for 1,000 hours. Then, the connection resistance between the SUS board of the bonding test piece B and the copper foil circuit of the flexible printed wiring board was measured using a resistance measuring device. The measurement results are shown in Table 1. In Table 1, the item "Conductivity after long-term damp heat test" is expressed as "85°C / 85%RH1000hr test" of conductivity. The case where the measured value of the connection resistance value is less than 0.3Ω is expressed as "A". The case where the measured value of the connection resistance value is greater than 0.3Ω and less than 1.0Ω is expressed as "B". The case where the measured value of the connection resistance value is greater than 1.0Ω is expressed as "C".

[0157] (viii) Electrical conductivity after welding (conductivity after welding, connection resistance) The bonding test piece B was floated in a 260° C. solder bath for 60 seconds. Then, the connection resistance between the SUS board of the bonding test piece B taken out of the solder bath and the copper foil circuit of the flexible printed wiring board was measured using a resistance value measuring instrument. The measurement results are shown in Table 1. In Table 1, the item "conductivity after welding (conductivity after welding, connection resistance)" is represented as "after normal wet welding test" of conductivity. The case where the measured value of the connection resistance value is less than 0.3Ω is represented as "A". The case where the measured value of the connection resistance value is 0.3Ω or more and less than 1.0Ω is represented as "B". The case where the measured value of the connection resistance value is 1.0Ω or more is represented as "C".

[0158] (ix) Flame retardancy The cover film was heat-cured at 160° C. for 2 hours, and flame retardancy was evaluated in accordance with UL-94. The evaluation results are shown in Table 1. The case that satisfies the judgment criteria of "VTM-0" (VTM-0 type) is indicated as "A". The case that does not satisfy the judgment criteria of "VTM-0" (VTM-1 type or VTM-2 type) is indicated as "F".

[0159] (x) Storage stability of adhesive composition The adhesive compositions of Examples 1 to 16 and Comparative Examples 1 to 4 having the compositions described in Table 1 (adhesive compositions) were placed in sealed glass flasks, stored at 5°C for a predetermined time, and the crystallinity of the compositions was observed. After the predetermined time, gelation or liquid separation of the adhesive composition was confirmed as poor storage stability, and the storage stability of the adhesive composition was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1. <Evaluation Criteria> A: No gelation or liquid separation was observed for more than one week. F: Gelation or liquid separation occurred in less than 1 week.

[0160] [Table 1]

[0161] The unit of the numerical value in each component column in the adhesive composition composition described in Table 1 is part by mass.

[0162] From the results shown in Table 1, it is understood that the adhesive compositions of Examples 1 to 16 provide cured products that are superior in soldering heat resistance even in a normal humidity environment and superior in long-term moisture and heat resistance, compared to the adhesive compositions of Comparative Examples 1 to 4. The adhesive composition, conductive filler (D) and flame retardant of Examples 3 to 16, the obtained cured product has excellent flame retardancy and conductivity. In Examples 2 to 6, the amount of epoxy resin (B) added was changed, but in Examples 4 to 6 in which 35 parts by mass or more of epoxy resin (B) was added to 100 parts by mass of polyester polyamide resin (A), the peeling strength after the normal wet soldering test was high. In particular, in Example 5 in which an imidazole compound (E) was added, the obtained adhesive composition also had excellent conductivity after the normal wet soldering test. In Example 11, an inorganic filler (F) was added to the adhesive composition, and the peeling strength after the normal wet soldering test was improved. In Example 12, an inorganic filler (F) and an organic filler (G) were added to the adhesive composition, and the peeling strength and conductivity after the normal wet soldering test were improved.

[0163] The disclosed contents of Japanese Patent Application No. 2022-109188 filed on July 6, 2022 are incorporated into this specification by reference in its entirety. All documents, patent applications, and technical specifications described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical specification was specifically and individually described as being incorporated by reference.

Claims

1. An adhesive composition comprising: A polyester polyamide resin (A) having a polyester portion and a polyamide portion; and Epoxy resin (B), The amount of the epoxy resin (B) is 1 to 60 parts by mass relative to 100 parts by mass of the polyester polyamide resin (A).

2. The adhesive composition according to claim 1, The amine value of the polyester polyamide resin (A) is 1.0 mgKOH / g to 12.0 mgKOH / g.

3. The adhesive composition according to claim 1, The polyester portion of the polyester polyamide resin (A) is a polycondensate of an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and an aliphatic diol having 2 to 54 carbon atoms, an aromatic diol having 2 to 54 carbon atoms or an alicyclic diol having 2 to 54 carbon atoms, The polyamide portion of the polyester polyamide resin (A) is a condensation product of a dicarboxylic acid containing an aliphatic dicarboxylic acid having 6 to 22 carbon atoms, an aromatic dicarboxylic acid having 6 to 22 carbon atoms and / or an alicyclic dicarboxylic acid having 6 to 22 carbon atoms and / or a dimerized aliphatic diacid having 20 to 48 carbon atoms and an aromatic diamine having 6 to 44 carbon atoms and / or a diamine having an alicyclic skeleton having 6 to 44 carbon atoms.

4. The adhesive composition according to claim 1, The adhesive composition further includes a polyurethane resin (C).

5. The adhesive composition according to claim 1, The water absorption of the cured product when immersed in water at 23° C. for 24 hours was 3% or less.

6. The adhesive composition according to claim 1, The adhesive composition further includes a conductive filler (D).

7. The adhesive composition according to claim 6, The content of the conductive filler (D) is 10 to 350 parts by mass based on 100 parts by mass of the total amount of the polyester polyamide resin (A), the epoxy resin (B), and the polyester urethane resin (C) which may be contained as an optional component in the adhesive composition.

8. The adhesive composition according to claim 1, The adhesive composition further includes an imidazole compound (E) having an alkoxysilyl group.

9. The adhesive composition according to claim 1, The adhesive composition further includes a non-conductive inorganic filler (F).

10. The adhesive composition according to claim 1, The adhesive composition further includes a non-conductive organic filler (G). 11 . A bonding film comprising: an adhesive composition layer in a B-stage state obtained by partially curing the adhesive composition according to claim 1 ; and a release film in contact with at least one surface of the adhesive composition layer.

12. A laminate with an adhesive composition layer, comprising an adhesive composition layer and a base film in contact with at least one surface of the adhesive composition layer, The adhesive composition layer is an adhesive composition layer composed of an uncured material of the adhesive composition according to any one of claims 1 to 10, an adhesive composition layer in a B-stage state in which a part of the adhesive composition is cured, or a cured layer in which the adhesive composition is cured. 13 . A laminate comprising a cured layer formed by curing the adhesive composition according to claim 1 . 14 . An electromagnetic wave shielding film comprising a cured layer formed by curing the adhesive composition according to claim 1 .

Citation Information

Patent Citations

  • Adhesive and flexible printed circuit board using the same

    JP2006152015A

  • Adhesive tape for tab

    JP2009040814A

  • Polyester amide resin composition

    JP2010031099A

  • Adhesive resin composition, coverlay, adhesive film, metal-clad laminate, and flexible printed wiring board

    JP2012025888A

  • Thermosetting adhesive composition and thermosetting adhesive sheet

    JP2015193683A